30 years of squeezed light generation - Andersen, Ulrik L.; Gehring, Tobias; Marquardt, Christoph; Leuchs, Gerd (Physica Scripta, 2016)
Squeezed light generation has come of age. Significant advances on squeezed light generation have been made over the last 30 years - from the initial, conceptual experiment in 1985 till today's top-tuned, application-oriented setups. Here we review the main experimental platforms for generating quadrature squeezed light that have been investigated in the last 30 years.
CRIS-Team Scopus Importer:2022-06-05
Keywords: entanglement; quantum optics; squeezed light

Addressing RB and CS transitions with a tunable source of photon pairs - Schunk, Gerhard; Vogl, Ulrich; Förtsch, Michael; Strekalov, Dmitry; Sedlmeir, Florian; Schwefel, Harald G.L.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2014)
CRIS-Team Scopus Importer:2022-06-05

After-gate attack on a quantum cryptosystem - Wiechers, C.; Lydersen, L.; Wittmann, C.; Elser, Dominique Alexander; Skaar, Johannes; Marquardt, Christoph; Makarov, V.; Leuchs, Gerd (New Journal of Physics, 2011)
We present a method to control the detection events in quantum key distribution systems that use gated single-photon detectors. We employ bright pulses as faked states, timed to arrive at the avalanche photodiodes outside the activation time. The attack can remain unnoticed, since the faked states do not increase the error rate per se. This allows for an intercept-resend attack, where an eavesdropper transfers her detection events to the legitimate receiver without causing any errors. As a side effect, afterpulses, originating from accumulated charge carriers in the detectors, increase the error rate. We have experimentally tested detectors of the system id3110 (Clavis2) from ID Quantique. We identify the parameter regime in which the attack is feasible despite the side effect. Furthermore, we outline how simple modifications in the implementation can make the device immune to this attack. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

A generator for unique quantum random numbers based on vacuum states - Gabriel, Christian; Wittmann, Christoffer; Sych, Denis; Dong, Ruifang; Mauerer, Wolfgang; Andersen, Ulrik L.; Marquardt, Christoph; Leuchs, Gerd (Nature Photonics, 2010)
Random numbers are a valuable component in diverse applications that range from simulations1 over gambling to cryptography2,3. The quest for true randomness in these applications has engendered a large variety of different proposals for producing random numbers based on the foundational unpredictability of quantum mechanics4-11. However, most approaches do not consider that a potential adversary could have knowledge about the generated numbers, so the numbers are not verifiably random and unique 12-15. Here we present a simple experimental setup based on homodyne measurements that uses the purity of a continuous-variable quantum vacuum state to generate unique random numbers. We use the intrinsic randomness in measuring the quadratures of a mode in the lowest energy vacuum state, which cannot be correlated to any other state. The simplicity of our source, combined with its verifiably unique randomness, are important attributes for achieving high-reliability, high-speed and lowcost quantum random number generators. © 2010 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Agile and Versatile Quantum Communication: Signatures and Secrets - Richter, Stefan; Thornton, Matthew; Khan, Imran; Scott, Hannah; Jaksch, Kevin; Vogl, Ulrich; Stiller, Birgit; Leuchs, Gerd; Marquardt, Christoph; Korolkova, Natalia (Physical Review X, 2021)
Agile cryptography allows for a resource-efficient swap of a cryptographic core in case the security of an underlying classical cryptographic algorithm becomes compromised. Conversely, versatile cryptography allows the user to switch the cryptographic task without requiring any knowledge of its inner workings. In this paper, we suggest how these related principles can be applied to the field of quantum cryptography by explicitly demonstrating two quantum cryptographic protocols, quantum digital signatures (QDS) and quantum secret sharing (QSS), on the same hardware sender and receiver platform. Crucially, the protocols differ only in their classical postprocessing. The system is also suitable for quantum key distribution (QKD) and is highly compatible with deployed telecommunication infrastructures, since it uses standard quadrature phase-shift keying encoding and heterodyne detection. For the first time, QDS protocols are modified to allow for postselection at the receiver, enhancing protocol performance. The cryptographic primitives QDS and QSS are inherently multipartite, and we prove that they are secure not only when a player internal to the task is dishonest, but also when (external) eavesdropping on the quantum channel is allowed. In our first proof-of-principle demonstration of an agile and versatile quantum communication system, the quantum states are distributed at GHz rates. A 1-bit message may be securely signed using our QDS protocols in less than 0.05 ms over a 2-km fiber link and in less than 0.2 s over a 20-km fiber link. To our knowledge, this also marks the first demonstration of a continuous-variable direct QSS protocol.
CRIS-Team Scopus Importer:2021-03-19

A High-Rate Receiver for Satellite Quantum Key Distribution - Rößler, Conrad; Günthner, Kevin; Hacker, Bastian; Leuchs, Gerd; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2022)
We present a high-rate fiber-integrated quantum receiver for phase-encoded satellite-based QKD. We highlight concepts for time synchronization as well as compensation of the Doppler shift and optimized quantum signal processing.
CRIS-Team Scopus Importer:2022-09-02

A high-speed secure quantum random number generator based on vacuum states - Gabriel, Christian; Wittmann, Christoffer; Hacker, Bastian; Mauerer, Wolfgang; Huntington, Elanor; Sabuncu, Metin; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
A high-speed continuous-variable quantum random bit generator with an expected effective bit generation rate of up to 10 GBit/s is presented. The obtained bit sequences are truly random and unique, i.e. they cannot be known by an adversary. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

All-fibre source of amplitude squeezed lightpulses - Meißner, Markus; Marquardt, Christoph; Heersink, Joel; Gaber, Tobias; Wietfeld, André; Leuchs, Gerd; Andersen, Ulrik Lund (Journal of Optics B Quantum and Semiclassical Optics, 2004)
An all-fibre source of amplitude squeezed solitons utilizing the self-phase modulation in an asymmetric Sagnac interferometer is experimentally demonstrated. The asymmetry of the interferometer is passively controlled by an integrated fibre coupler, allowing for the optimization of the noise reduction. We have carefully studied the dependence of the amplitude noise on the asymmetry and the power launched into the Sagnac interferometer. Qualitatively, we find good agreement between the experimental results, a semi-classical theory and earlier numerical calculations (Schmitt et al 1998 Phys. Rev. Lett. 81 2446). The stability and flexibility of this all-fibre source makes it particularly well suited to applications in quantum information science.<br
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.optik.1optik.allfib

An optimized photon pair source for quantum circuits - Harder, Georg; Ansari, Vahid; Brecht, Benjamin; Dirmeier, Thomas; Marquardt, Christoph; Silberhorn, Christine (Optics Express, 2013)
We implement an ultrafast pulsed type-II parametric down conversion source in a periodically poled KTP waveguide at telecommunication wavelengths with almost identical properties between signal and idler. As such, our source resembles closely a pure, genuine single mode photon pair source with indistinguishable modes. We measure the joint spectral intensity distribution and second order correlation functions of the marginal beams and find with both methods very low effective mode numbers corresponding to a Schmidt number below 1.16. We further demonstrate the indistinguishability as well as the purity of signal and idler photons by Hong-Ou-Mandel interferences between signal and idler and between signal/idler and a coherent field, respectively. Without using narrowband spectral filtering, we achieve a visibility for the interference between signal and idler of 94.8% and determine a purity of more than 80% for the heralded single photon states. Moreover, we measure raw heralding efficiencies of 20.5% and 15.5% for the signal and idler beams corresponding to detector-loss corrected values of 80% and 70%. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

A robust quantum receiver for phase shift keyed signals - Mueller, C. R.; Marquardt, Christoph (New Journal of Physics, 2015)
The impossibility of perfectly discriminating non-orthogonal quantum states imposes far-reaching consequences both on quantum and classical communication schemes. We propose and numerically analyze an optimized quantum receiver for the discrimination of phase encoded signals. Our scheme outperforms the standard quantum limit and approaches the Helstrom bound for any signal power. The discrimination is performed via an optimized, feedback-mediated displacement prior to a photon counting detector. We provide a detailed analysis of the influence of excess noise and technical imperfections on the average error probability. The results demonstrate the receiver's robustness and show that it can outperform any classical receiver over a wide range of realistic parameters.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Coherent communication; Optical communication; Quantum information processing; Quantum noise; Quantum receiver

Assessing the polarization of a quantum field from stokes fluctuations - Klimov, A. B.; Bjoerk, G.; Soederholm, J.; Madsen, L. S.; Lassen, M.; Andersen, U. L.; Heersink, J.; Dong, Ruifang; Marquardt, Christoph; Leuchs, Gerd; Sanchez-Soto, L. L. (Physical Review Letters, 2010)
We propose an operational degree of polarization in terms of the variance of the Stokes vector minimized over all the directions of the Poincaré sphere. We examine the properties of this second-order definition and carry out its experimental determination. Quantum states with the same standard (first-order) degree of polarization are correctly discriminated by this new measure. We argue that a comprehensive quantum characterization of polarization properties requires a whole hierarchy of higher-order degrees. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, Bettina; Elser, Dominique Alexander; Bartley, Tim; Sabuncu, Metin; Wittmann, Christoffer; Sych, Denis; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2010)
We investigate the properties of an atmospheric channel for free space quantum communication with continuous polarization variables. In our prepare-and-measure setup, coherent polarization states are transmitted through an atmospheric quantum channel of 100 m length on the flat roof of our institute's building. The signal states are measured by homodyne detection with the help of a local oscillator (LO) which propagates in the same spatial mode as the signal, orthogonally polarized to it. Thus the interference of signal and LO is excellent and atmospheric fluctuations are auto-compensated. The LO also acts as a spatial and spectral filter, which allows for unrestrained daylight operation. Important characteristics for our system are atmospheric channel influences that could cause polarization, intensity and position excess noise. Therefore we study these influences in detail. Our results indicate that the channel is suitable for our quantum communication system in most weather condition
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.optik.1optik.atmosp

Atmospheric continuous-variable quantum communication - Heim, B.; Peuntinger, Christian; Killoran, N.; Khan, Imran; Wittmann, C.; Marquardt, Christoph; Leuchs, Gerd (New Journal of Physics, 2014)
We present a quantum communication experiment conducted over a point-to-point free-space link of 1.6 km in urban conditions. We study atmospheric influences on the capability of the link to act as a continuous-variable (CV) quantum channel. Continuous polarization states (that contain the signal encoding as well as a local oscillator (LO) in the same spatial mode) are prepared and sent over the link in a polarization multiplexed setting. Both signal and LO undergo the same atmospheric fluctuations. These are intrinsically auto-compensated which removes detrimental influences on the interferometric visibility. At the receiver, we measure the Q-function and interpret the data using the framework of effective entanglement (EE). We compare different state amplitudes and alphabets (two-state and four-state) and determine their optimal working points with respect to the distributed EE. Based on the high entanglement transmission rates achieved, our system indicates the high potential of atmospheric links in the field of CV quantum key distribution.
CRIS-Team Scopus Importer:2022-06-05
Keywords: atmospheric turbulence; polarization in atmospheric optics; quantum communication

Atomic mercury vapor inside a hollow-core photonic crystal fiber - Vogl, Ulrich; Peuntinger, Christian; Joly, Nicolas Y.; Russell, Philip St. J.; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2014)
We demonstrate high atomic mercury vapor pressure in a kagomé-style hollow-core photonic crystal fiber at room temperature. After a few days of exposure to mercury vapor the fiber is homogeneously filled and the optical depth achieved remains constant. With incoherent optical pumping from the ground state we achieve an optical depth of 114 at the 63P2 - 63D3 transition, corresponding to an atomic mercury number density of 6 × 1010cm-3. The use of mercury vapor in quasi one-dimensional confinement may be advantageous compared to chemically more active alkali vapor, while offering strong optical nonlinearities in the ultraviolet region of the optical spectrum.
CRIS-Team Scopus Importer:2022-06-05

Attacks on practical quantum key distribution systems (and how to prevent them) - Jain, Nitin; Stiller, Birgit; Khan, Imran; Elser, Dominique Alexander; Marquardt, Christoph; Leuchs, Gerd (Contemporary Physics, 2016)
With the emergence of an information society, the idea of protecting sensitive data is steadily gaining importance. Conventional encryption methods may not be sufficient to guarantee data protection in the future. Quantum key distribution (QKD) is an emerging technology that exploits fundamental physical properties to guarantee perfect security in theory. However, it is not easy to ensure in practice that the implementations of QKD systems are exactly in line with the theoretical specifications. Such theory–practice deviations can open loopholes and compromise security. Several such loopholes have been discovered and investigated in the last decade. These activities have motivated the proposal and implementation of appropriate countermeasures, thereby preventing future attacks and enhancing the practical security of QKD. This article introduces the so-called field of quantum hacking by summarising a variety of attacks and their prevention mechanisms.
CRIS-Team Scopus Importer:2021-06-29
Keywords: countermeasures; practical data security; quantum computer; Quantum cryptography; quantum hacking; quantum key distribution

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Leuchs, Gerd; Silberhorn, Christine; Marquardt, Christoph (Nature Communications, 2013)
The generation of high-quality single-photon states with controllable narrow spectral bandwidths and central frequencies is key to facilitate efficient coupling of any atomic system to non-classical light fields. Such an interaction is essential in numerous experiments for fundamental science and applications in quantum communication and information processing, as well as in quantum metrology. Here we implement a fully tunable, narrow-band and efficient single-photon source based on a whispering gallery mode resonator. Our disk-shaped, monolithic and intrinsically stable resonator is made of lithium niobate and supports a cavity-assisted spontaneous parametric down-conversion process. The generated photon pairs are emitted into two highly tunable resonator modes. We verify wavelength tuning over 100 nm of both modes with controllable bandwidth between 7.2 and 13 MHz. Heralding of single photons yields anti-bunching with g (2) (0)<0.2. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Binary Homodyne Detection for Observing Quadrature Squeezing in Satellite Links - Müller, Christian R.; Seshadreesan, Kaushik P.; Peuntinger, Christian; Marquardt, Christoph (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
Optical satellite links open up new prospects for realizing quantum physical experiments over unprecedented length scales. We demonstrate the feasibility of quadrature squeezing detection in satellite links using optical communication technology already in orbit. The detection process is complicated by the fact that the homo dyne detectors aboard of satellites often provide an efficient resolution of only one bit. We show experimentally, that despite this extremal constraint quantum squeezing can still be detected efficiently. The required sample overhead compared to an ideal homo dyne detector is only a factor of 3.3.
CRIS-Team Scopus Importer:2019-05-21

Binary homodyne detection for observing quadrature squeezing in satellite links - Müller, Christian; Seshadreesan, Kaushik P.; Peuntinger, Christian; Marquardt, Christoph (Physical Review Research, 2020)
Optical satellite links open up new prospects for realizing quantum physical experiments over unprecedented length scales. We analyze and affirm the feasibility of detecting quantum squeezing in an optical mode with homodyne detection of only one bit resolution, as is found in satellites already in orbit. We show experimentally that, in combination with a coherent displacement, a binary homodyne detector can still detect quantum squeezing efficiently even under high loss. The sample overhead in comparison to nondiscretized homodyne detection is merely a factor of 3.3.
CRIS-Team WoS Importer:2021-01-22

Birefringence and dispersion of cylindrically polarized modes in nanobore photonic crystal fiber - Euser, T. G.; Schmidt, M. A.; Joly, N. Y.; Gabriel, C.; Marquardt, Christoph; Zang, L. Y.; Foertsch, M.; Banzer, Peter; Brenn, A.; Elser, Dominique; Scharrer, Michael G; Leuchs, Gerd; et al. (Journal of the Optical Society of America B-Optical Physics, 2011)
We demonstrate experimentally and theoretically that a nanoscale hollow channel placed centrally in the solidglass core of a photonic crystal fiber strongly enhances the cylindrical birefringence (the modal index difference between radially and azimuthally polarized modes). Furthermore, it causes a large split in group velocity and group velocity dispersion. We show analytically that all three parameters can be varied over a wide range by tuning the diameters of the nanobore and the core.© 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Characterization and application of continuous variable quantum states of light - Marquardt, Christoph (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2007)
The aim of this thesis was the characterization of continuous variable quantum states of light and their application in quantum information processing protocols. The photo current statistics of squeezed and entangled states from a nonlinear fiber Sagnac interferometer were analyzed and can be regarded as Gaussian states within the measurement accuracy. In addition, instead of the usual variance, the covariance was experimentally investigated as a relative measure of squeezing, using a balanced self-homodyne system. As an application in a quantum information protocol the experimental distillation of squeezed states has been shown. The undistilled squeezed states suffered from non-Gaussian classical excess noise. In the experiment nearly the complete squeezing could be recovered by a probabilistic selection method. The Cavalcanti-Reid criterion to prove intrinsic macroscopic superposition states in continuous variables was experimentally applied for the first time. With this criterion generalized superposition states were proven in vacuum and intense coherent states with a distance in phase space of 0.51+/-0.02 shot noise units. For squeezed states from an optical parametric oscillator generalized superposition states were proven with a distance of up to 0.83+/-0.02 shot noise units. At the same time the dependence of the criterion on squeezing and purity of the states was investigated. To reconstruct the quantum state of the polarization variables of light, a theory was developed, that is based on the su(2) algebra and at the same time takes into account the possibility, that the photon number is not fixed. It was found that for high photon numbers the quantum state reconstruction of the SU(2) Q function in Poincare space is an inverse 3D Radon transformation. With this method the Q function of a polarization squeezed state was reconstructed from measured data. In the dark plane of a polarization squeezed state the Wigner function of an intense Kerr squeezed state was reconstructed for the first time.<br
Keywords: quantum state reconstruction; quantum state distillation; photon statistics; Squeezed state

Classical and quantum properties of cylindrically polarized beams of light via a poincaré sphere representation - Holleczek, A.; Aiello, A.; Gabriel, C.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Classical and quantum properties of cylindrically polarized states of light - Holleczek, Annemarie; Aiello, Andrea; Gabriel, Christian; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2011)
We investigate theoretical properties of beams of light with non-uniform polarization patterns. Specifically, we determine all possible configurations of cylindrically polarized modes (CPMs) of the electromagnetic field, calculate their total angular momentum and highlight the subtleties of their structure. Furthermore, a hybrid spatio-polarization description for such modes is introduced and developed. In particular, two independent Poincaré spheres have been introduced to represent simultaneously the polarization and spatial degree of freedom of CPMs. Possible mode-to-mode transformations accomplishable with the help of Bconventional polarization and spatial phase retarders are shown within this representation. Moreover, the importance of these CPMs in the quantum optics domain due to their classical features is highlighted. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Classical entanglement in polarization metrology - Toeppel, Falk; Aiello, Andrea; Marquardt, Christoph; Giacobino, Elisabeth; Leuchs, Gerd (New Journal of Physics, 2014)
Quantum approaches relying on entangled photons have been recently proposed to increase the efficiency of optical measurements. We demonstrate here that, surprisingly, the use of classical light with entangled degrees of freedom can also bring outstanding advantages over conventional measurements in polarization metrology. Specifically, we show that radially polarized beams of light allow to perform real-time single-shot Mueller matrix polarimetry. Our results also indicate that quantum optical procedures requiring entanglement without nonlocality can be actually achieved in the classical optics regime. © 2014 IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05
Keywords: applied classical electromagnetism; entanglement and quantum nonlocality; polarization

Classical entanglement: Theory and application - Töppel, F.; Aiello, A.; Marquardt, Christoph; Giacobino, E.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2022-06-05

Classically entangled optical beams for high-speed kinematic sensing - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, Marco; Giacobino, Elisabeth; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optica, 2015)
Tracking the kinematics of fast-moving objects is an important diagnostic tool for science and engineering. Here, we demonstrate an approach to positional and directional sensing based on the concept of classical entanglement in vector beams of light [Found. Phys. 28, 361–374 (1998)]. The measurement principle relies on the intrinsic correlations existing in such beams between transverse spatial modes and polarization. The latter can be determined from intensity measurements with only a few fast photodiodes, greatly outperforming the bandwidth of current CCD/CMOS devices. In this way, our setup enables two-dimensional real-time sensing with temporal resolution in the GHz range. We expect the concept to open up new directions in metrology and sensing.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Classical and quantum physics; Optical sensing and sensors

Cluster state generation with quadrature squeezed cylindrically polarized modes - Gabriel, Christian; Rigas, Ioannes; Aiello, Andrea; Berg-Johansen, Stefan; van Loock, Peter; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We present schemes which exploit the hybrid-entanglement in quadrature squeezed cylindrically polarized modes to generate cluster states. Such states are essential for one-way quantum computing. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Concentrating the phase of a coherent state by means of probabilistic amplification - Usuga, Mario A.; Mueller, Christian R.; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Leuchs, Gerd; Andersen, Ulrik L. (AIP Conference Proceedings, 2011)
We discuss the recent implementation of phase concentration of an optical coherent state by use of a probabilistic noiseless amplifier. The operation of the amplifier is described pictorially with phase space diagrams, and the experimental results are outlined. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Noiseless amplification; Phase concentration; Phase variance

Concentration of phase-information - Usuga, Mario; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Andersen, Ulrik L.A.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2010)
We demonstrate a probabilistic scheme capable of increasing the phase information of weak coherent states by addition of thermal noise and subsequent photon-counting based postselection. We present experimental and theoretical results. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Continuously adjustable narrow-band heralded single photon source - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We present the high efficient generation of narrow-band heralded single photons, widely tunable in wavelength and bandwidth using resonator enhanced spontaneous down conversion in a crystalline whispering gallery mode resonator. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Continuous-variable entanglement distillation of non-Gaussian mixed states - Dong, Ruifang; Lassen, Mikael; Heersink, Joel; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd; Andersen, Ulrik L. (Physical Review A - Atomic, Molecular, and Optical Physics, 2010)
Many different quantum-information communication protocols such as teleportation, dense coding, and entanglement-based quantum key distribution are based on the faithful transmission of entanglement between distant location in an optical network. The distribution of entanglement in such a network is, however, hampered by loss and noise that is inherent in all practical quantum channels. Thus, to enable faithful transmission one must resort to the protocol of entanglement distillation. In this paper we present a detailed theoretical analysis and an experimental realization of continuous variable entanglement distillation in a channel that is inflicted by different kinds of non-Gaussian noise. The continuous variable entangled states are generated by exploiting the third order nonlinearity in optical fibers, and the states are sent through a free-space laboratory channel in which the losses are altered to simulate a free-space atmospheric channel with varying losses. We use linear optical components, homodyne measurements, and classical communication to distill the entanglement, and we find that by using this method the entanglement can be probabilistically increased for some specific non-Gaussian noise channels. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Continuous variable entanglement distillation of non-gaussian states - Lassen, Mikael Ostergaard; Dong, Ruifang; Heersink, Joel; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd; Ulrik, L. Andersen (AIP Conference Proceedings, 2009)
We experimentally demonstrate distillation of continuous variable entangled light that has undergone non-Gaussian attenuation loss. The continuous variable entanglement is generated with optical fibers and sent through a lossy channel, where the transmission is varying in time. By employing simple linear optical components, a measurement induced operation and classical communication, we demonstrate that the entanglement is probabilistically increased. © 2009 American Institute of Physics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Distillation; Entanglement; Quantum information

Continuous variable free space quantum communication - Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2016)
Continuous variable free space quantum communication offers high-speed distribution of quantum states for quantum key distribution under daylight condition. We report our activities on experimental investigations ranging from intra-city links to satellite based communication.
CRIS-Team Scopus Importer:2022-06-05

Decorrelated PDC source at telecom wavelengths with identical signal and idler - Harder, Georg; Ansari, Vahid; Brecht, Benjamin; Dirmeier, Thomas; Marquardt, Christoph; Silberhorn, Christine (Optics InfoBase Conference Papers, 2013)
CRIS-Team Scopus Importer:2022-06-05

Demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
We demonstrate and discuss a state of light with purely transverse angular momentum - a photonic wheel - generated by tight focusing of polarization tailored light. We use an experimental nanoprobing technique to measure the corresponding distribution.
CRIS-Team Scopus Importer:2022-06-05

Depolarized guided acoustic wave Brillouin scattering in hollow-core photonic crystal fibers - Zhong, Wenjia; Stiller, Birgit; Elser, Dominique Alexander; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2015)
By performing quantum-noise-limited optical heterodyne detection, we observe polarization noise in light after propagation through a hollow-core photonic crystal fiber (PCF). We compare the noise spectrum to the one of a standard fiber and find an increase of noise even though the light is mainly transmitted in air in a hollow-core PCF. Combined with our simulation of the acoustic vibrational modes in the hollow-core PCF, we are offering an explanation for the polarization noise with a variation of guided acoustic wave Brillouin scattering (GAWBS). Here, instead of modulating the strain in the fiber core as in a solid core fiber, the acoustic vibrations in hollow-core PCF influence the effective refractive index by modulating the geometry of the photonic crystal structure. This induces polarization noise in the light guided by the photonic crystal structure.
CRIS-Team Scopus Importer:2021-06-29

Detecting the spatial quantum uncertainty of bosonic systems - Chille, Vanessa; Treps, Nicolas; Fabre, Claude; Leuchs, Gerd; Marquardt, Christoph; Aiello, Andrea (New Journal of Physics, 2016)
We present the quantum theory of direct detection of bosonic particles by multipixel detectors. For the sake of clarity, we specialize on beams of photons, and we study the measurement of different spatial beam characteristics, as position and width. The limits of these measurements are set by the quantum nature of the light field. We investigate how both, detector imperfections and finite pixel size affect the photon counting distribution. An analytic theory for the discretized detection setup is derived. We discuss the results and compare them to the theory presented by Chille et al 2015 Opt. Express 23 32777, which investigates the beam width noise independently of the measurement system. Finally, we present numerical simulations that furnish realistic and promising predictions for possible experimental studies.
CRIS-Team Scopus Importer:2022-06-05
Keywords: bosonic systems; quantum uncertainty; spatial measurements

Device Calibration Impacts Security of Quantum Key Distribution - Jain, Nitin; Wittmann, Christoffer; Lydersen, Lars; Wiechers, Carlos; Elser, Dominique Alexander; Marquardt, Christoph; Makarov, Vadim; Leuchs, Gerd (Physical Review Letters, 2011)
Characterizing the physical channel and calibrating the cryptosystem hardware are prerequisites for establishing a quantum channel for quantum key distribution (QKD). Moreover, an inappropriately implemented calibration routine can open a fatal security loophole. We propose and experimentally demonstrate a method to induce a large temporal detector efficiency mismatch in a commercial QKD system by deceiving a channel length calibration routine. We then devise an optimal and realistic strategy using faked states to break the security of the cryptosystem. A fix for this loophole is also suggested. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Direct experimental test of non-separability and other quantum techniques using continuous variables of light - Korolkova, Natalia; Silberhorn, Christine; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (European Physical Journal D, 2002)
We present schemes for the generation and evaluation of continuous variable entanglement of bright optical beams and give a brief overview of a variety of optical techniques and quantum communication applications on this basis. A new entanglement-based quantum interferometry scheme with bright beams is suggested. The performance of the presented schemes is independent of the relative interference phase which is advantageous for quantum communication applications. © EDP Sciences, Springer-Verlag, Società Italiana di Fisica 2002.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.direct

Direct measurement of the geometric spin hall effect of light - Korger, Jan; Aiello, Andrea; Chille, Vanessa; Wittmann, Christoffer; Banzer, Peter; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Frontiers in Optics, FIO 2012, 2012)
We experimentally demonstrate a recently predicted novel beam shift phenomenon, the geometric spin Hall effect of light. This effect is fundamentally different from ordinary beam shifts due to its purely geometric nature. © OSA 201

Distillation of Squeezing from Non-Gaussian Quantum States - Heersink, Joel; Marquardt, Christoph; Dong, Ruifang; Filip, Radim; Lorenz, Stefan; Leuchs, Gerd; Andersen, Ulrik Lund (Physical Review Letters, 2006)
We show that single copy distillation of squeezing from continuous variable non-Gaussian states is possible using linear optics and conditional homodyne detection. A specific non-Gaussian noise source, corresponding to a random linear displacement, is investigated experimentally. Conditioning the signal on a tap measurement, we observe probabilistic recovery of squeezing. © 2006 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.optik.1optik.distil

Distillation of squeezing using an engineered pulsed parametric down-conversion source - Dirmeier, Thomas; Tiedau, Johannes; Khan, Imran; Ansari, Vahid; Müller, Christian; Silberhorn, Christine; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2020)
Hybrid quantum information processing combines the advantages of discrete and continues variable protocols by realizing protocols consisting of photon counting and homodyne measurements. However, the mode structure of pulsed sources and the properties of the detection schemes often require the use of optical filters in order to combine both detection methods in a common experiment. This limits the efficiency and the overall achievable squeezing of the experiment. In our work, we use photon subtraction to implement the distillation of pulsed squeezed states originating from a genuinely spatially and temporally single-mode parametric down-conversion source in non-linear waveguides. Due to the distillation, we witness an improvement of 0.17 dB from an initial squeezing value of -1.648 +/- 0.002 dB, while achieving a purity of 0.58, and confirm the non-Gaussianity of the distilled state via the higher-order cumulants. With this, we demonstrate the source's suitability for scalable hybrid quantum network applications with pulsed quantum light. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2020-11-13

Distributing entanglement with separable states - Peuntinger, Christian; Chille, Vanessa; Mista, Ladislav; Korolkova, Natalia; Foertsch, Michael; Korger, Jan; Marquardt, Christoph; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2013)
We experimentally demonstrate a protocol for entanglement distribution by a separable quantum system. In our experiment, two spatially separated modes of an electromagnetic field get entangled by local operations, classical communication, and transmission of a correlated but separable mode between them. This highlights the utility of quantum correlations beyond entanglement for the establishment of a fundamental quantum information resource and verifies that its distribution by a dual classical and separable quantum communication is possible. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Distribution of squeezed states through an atmospheric channel - Peuntinger, Christian; Heim, Bettina; Mueller, Christian R.; Gabriel, Christian; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2014)
Continuous variable quantum states of light are used in quantum information protocols and quantum metrology and known to degrade with loss and added noise. We were able to show the distribution of bright polarization squeezed quantum states of light through an urban free-space channel of 1.6 km length. To measure the squeezed states in this extreme environment, we utilize polarization encoding and a postselection protocol that is taking into account classical side information stemming from the distribution of transmission values. The successful distribution of continuous variable squeezed states is accentuated by a quantum state tomography, allowing for determining the purity of the state. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Eavesdropper localization for quantum and classical channels via nonlinear scattering - Popp, Alexandra; Sedlmeir, Florian; Stiller, Birgit; Marquardt, Christoph (Optica Quantum, 2024)
Optical fiber networks are part of the important critical infrastructure and known to be prone to eavesdropping attacks. Hence, cryptographic methods have to be used to protect communication. Quantum key distribution (QKD), at its core, offers information theoretical security based on the laws of physics. In deployments, one has to take into account practical security and resilience. The latter includes the localization of a possible eavesdropper after an anomaly has been detected by the QKD system to avoid denial-of-service. Here, we present an approach to eavesdropper location that can be employed in quantum as well as classical channels using stimulated Brillouin scattering. The tight localization of the acoustic wave inside the fiber channel using correlated pump and probe waves allows discovery of the coordinates of a potential threat within centimeters. We demonstrate that our approach outperforms conventional optical time-domain reflectometry (OTDR) in the task of localizing an evanescent outcoupling of 1% with centimeter precision inside standard optical fibers. The system is furthermore able to clearly distinguish commercially available standard SMF28 from different manufacturers, paving the way for fingerprinted fibers in high-security environments.<br

Efficient generation of temporally shaped photons using nonlocal spectral filtering - Averchenko, Valentin; Sych, Denis; Marquardt, Christoph; Leuchs, Gerd (Physical Review A, 2020)
We study the generation of single-photon pulses with the tailored temporal shape via nonlocal spectral filtering. A shaped photon is heralded from a time-energy entangled photon pair upon spectral filtering and time-resolved detection of its entangled counterpart. We show that the temporal shape of the heralded photon is defined by the time-inverted impulse response of the spectral filter and does not depend on the heralding instant. Thus one can avoid postselection of particular heralding instants and achieve a substantially higher heralding rate of shaped photons as compared to the generation of photons via nonlocal temporal modulation. Furthermore, the method can be used to generate shaped photons with a coherence time in the ns-mu s range and is particularly suitable to produce photons with the exponentially rising temporal shape required for efficient interfacing to a single quantum emitter in free space.
CRIS-Team WoS Importer:2020-01-24

Efficient microwave to optical photon conversion: An electro-optical realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G. L. (Optica, 2016)
Linking classical microwave electrical circuits to the optical telecommunication band is at the core of modern communication. Future quantum information networks will require coherent microwave-to-optical conversion to link electronic quantum processors and memories via low-loss optical telecommunication networks. Efficient conversion can be achieved with electro-optical modulators operating at the single microwave photon level. In the standard electro-optic modulation scheme, this is impossible because both up- and down-converted sidebands are necessarily present. Here, we demonstrate true single-sideband up- or down-conversion in a triply resonant whispering gallery mode resonator by explicitly addressing modes with asymmetric free spectral range. Compared to previous experiments, we show a 3 orders of magnitude improvement of the electro-optical conversion efficiency, reaching 0.1% photon number conversion for a 10 GHz microwave tone at 0.42 mW of optical pump power. The presented scheme is fully compatible with existing superconducting 3D circuit quantum electrodynamics technology and can be used for nonclassical state conversion and communication. Our conversion bandwidth is larger than 1 MHz and is not fundamentally limited.
CRIS-Team Scopus Importer:2021-06-29

Efficient single sideband microwave to optical conversion using a LiNbO3 WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dimitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We present a coherent microwave to telecom signal converter based on the electro-optical effect using a crystalline WGM-resonator coupled to a 3D microwave cavity, achieving high photon conversion efficiency of 0.1% with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Enhanced free space beam capture by improved optical tapers - Bartley, Tim; Heim, Bettina; Elser, Dominique Alexander; Sych, Denis; Sabuncu, Metin; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (2010)
In our continuous variable quantum key distribution (QKD) scheme, the homodyne detection set-up requires balancing the intensity of an incident beam between two photodiodes. Realistic lens systems are insufficient to provide a spatially stable focus in the presence of large spatial beam-jitter caused by atmospheric transmission. We therefore present an improved geometry for optical tapers which offer up to four times the angular tolerance of a lens. The effective area of a photodiode can thus be increased, without decreasing its bandwidth. This makes them suitable for use in our free space QKD experiment and in free space optical communication in general. © Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering 201
Keywords: Atmospheric optics; Beam-jitter; Free space communication; Optical taper; Quantum key distribution; Random media

Entanglement creation by locally splitting a discordant state - Croal, Callum; Mišta, Ladislav; Chille, Vanessa; Peuntinger, Christian; Marquardt, Christoph; Leuchs, Gerd; Korolkova, Natalia (Optics InfoBase Conference Papers, 2014)
We introduce and experimentally implement counter-intuitive entanglement creation by locally splitting a classical mode that is part of a larger discordant state. Possible applications are quantum advantage in information encoding and assisted dense coding. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Entanglement of Gaussian states and the applicability to quantum key distribution over fading channels - Usenko, Vladyslav C.; Heim, Bettina; Peuntinger, Christian; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd; Filip, Radim (New Journal of Physics, 2012)
Entanglement properties of Gaussian states of light as well as the security of continuous variable quantum key distribution with Gaussian states in free-space fading channels are studied. These qualities are shown to be sensitive to the statistical properties of the transmittance distribution in the cases when entanglement is strong or when channel excess noise is present. Fading, i.e. transmission fluctuations, caused by beam wandering due to atmospheric turbulence, is a frequent challenge in free-space communication. We introduce a method of fading discrimination and subsequent post-selection of the corresponding sub-states and show that it can improve the entanglement resource and restore the security of the key distribution over a realistic fading link. Furthermore, the optimal post-selection strategy in combination with an optimized entangled resource is shown to drastically increase the protocol's robustness to excess noise, which is confirmed for experimentally measured fading channel characteristics. The stability of the result against finite data ensemble size and imperfect channel estimation is also addressed. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

Entangling different degrees of freedom by quadrature squeezing cylindrically polarized modes - Gabriel, C.; Aiello, Andrea; Zhong, W.; Euser, T. G.; Joly, N. Y.; Banzer, Peter; Foertsch, M.; Elser, Dominique; Andersen, U. L.; Marquardt, Christoph; Russell, P. St. J.; Leuchs, Gerd (Physical Review Letters, 2011)
Quantum systems such as, for example, photons, atoms, or Bose-Einstein condensates, prepared in complex states where entanglement between distinct degrees of freedom is present, may display several intriguing features. In this Letter we introduce the concept of such complex quantum states for intense beams of light by exploiting the properties of cylindrically polarized modes. We show that already in a classical picture the spatial and polarization field variables of these modes cannot be factorized. Theoretically it is proven that by quadrature squeezing cylindrically polarized modes one generates entanglement between these two different degrees of freedom. Experimentally we demonstrate amplitude squeezing of an azimuthally polarized mode by exploiting the nonlinear Kerr effect in a specially tailored photonic crystal fiber. These results display that such novel continuous-variable entangled systems can, in principle, be realized.© 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Entangling the Whole by Beam Splitting a Part - Croal, Callum; Peuntinger, Christian; Chille, Vanessa; Marquardt, Christoph; Leuchs, Gerd; Korolkova, Natalia; Mista, Ladislav (Physical Review Letters, 2015)
A beam splitter is a basic linear optical element appearing in many optics experiments and is frequently used as a continuous-variable entangler transforming a pair of input modes from a separable Gaussian state into an entangled state. However, a beam splitter is a passive operation that can create entanglement from Gaussian states only under certain conditions. One such condition is that the input light is suitably squeezed. We demonstrate, experimentally, that a beam splitter can create entanglement even from modes which do not possess such a squeezing provided that they are correlated to, but not entangled with, a third mode. Specifically, we show that a beam splitter can create three-mode entanglement by acting on two modes of a three-mode fully separable Gaussian state without entangling the two modes themselves. This beam splitter property is a key mechanism behind the performance of the protocol for entanglement distribution by separable states. Moreover, the property also finds application in collaborative quantum dense coding in which decoding of transmitted information is assisted by interference with a mode of the collaborating party.
CRIS-Team Scopus Importer:2022-06-05

Evading Vacuum Noise: Wigner Projections or Husimi Samples? - Mueller, C. R.; Peuntinger, Christian; Dirmeier, T.; Khan, Imran; Vogl, Ulrich; Marquardt, Christoph; Leuchs, Gerd; Sanchez-Soto, L. L.; Teo, Y. S.; Hradil, Zdenek; Rehacek, Jaroslav (Physical Review Letters, 2016)
The accuracy in determining the quantum state of a system depends on the type of measurement performed. Homodyne and heterodyne detection are the two main schemes in continuous-variable quantum information. The former leads to a direct reconstruction of the Wigner function of the state, whereas the latter samples its Husimi Q function. We experimentally demonstrate that heterodyne detection outperforms homodyne detection for almost all Gaussian states, the details of which depend on the squeezing strength and thermal noise.
CRIS-Team Scopus Importer:2022-06-05

Experimental Demonstration of Continuous Variable Entanglement Distillation - Dong, Ruifang; Lassen, Mikael Ostergaard; Marquardt, Christoph; Filip, Radim; Andersen, Ulrik Lund; Leuchs, Gerd (Quantum Electronics and Laser Science Conference 2008, 2008)
We experimentally demonstrate distillation of continuous variable entanglement through an attenuating quantum channel. Through a simple protocol based entirely on linear optics and homodyne detection we probabilistically filter out a highly entangled state from a less non-entangled mixed state.<br

Experimental demonstration of macroscopic quantum coherence in Gaussian states - Marquardt, Christoph; Andersen, Ulrik L.; Leuchs, Gerd; Takeno, Yuishi; Yukawa, Mitsuyoshi; Yonezawa, Hidehiro; Furusawa, Akira (Physical Review A, 2007)
We witness experimentally the presence of macroscopic coherence in Gaussian quantum states using a recently proposed criterion. The macroscopic coherence stems from interference between macroscopically distinct states in phase space, and we prove experimentally that a coherent state contains these features with a distance in phase space of 0.51±0.02 shot noise units. This is surprising because coherent states are generally considered being at the border between classical and quantum states, not yet displaying any nonclassical effect. For squeezed and entangled states the effect may be larger but depends critically on the state purity. © 2007 The American Physical Societ
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.experi_8

Experimental demonstration of the geometric spin hall effect of light in highly focused vector beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Lindlein, Norbert; Aiello, Andrea; Marquardt, Christoph; Korger, Jan; Leuchs, Gerd (Quantum Electronics and Laser Science Conference, QELS 2012, 2012)
We demonstrate the geometric spin Hall effect of light by focusing a specially polarization tailored beam of light, resulting in the generation of purely transverse angular momentum in the focal plane. © 2012 OS

Experimental Distillation of Squeezed States - Heersink, Joel; Marquardt, Christoph; Filip, Radim; Dong, Ruifang; Chekhova, Maria V.; Lorenz, S.; Leuchs, Gerd; Andersen, Ulrik Lund (QThL3 Quantum Electronics and Laser Science Conference (CLEO:FS), 2006)
We report on the first experimental distillation of an intense squeezed state from a non-Gaussian mixture of polarization squeezed states. Conditioning the signal on a tap measurement, we observe probabilistic recovery of the squeezing.<br

Experimental entanglement distillation of mesoscopic quantum states - Dong, Ruifang; Lassen, Mikael; Heersink, Joel; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd; Andersen, L. Ulrik (Nature Physics, 2008)
The distribution of entangled states between distant parties in an optical network is crucial for the successful implementation of various quantum communication protocols such as quantum cryptography, teleportation and dense coding. However, owing to the unavoidable loss in any real optical channel, the distribution of loss-intolerant entangled states is inevitably afflicted by decoherence, which causes a degradation of the transmitted entanglement. To combat the decoherence, entanglement distillation, a process of extracting a small set of highly entangled states from a large set of less entangled states, can be used. Here we report on the distillation of deterministically prepared light pulses entangled in continuous variables that have undergone non-Gaussian noise. The entangled light pulses are sent through a lossy channel, where the transmission is varying in time similarly to light propagation in the atmosphere. By using linear optical components and global classical communication, the entanglement is probabilisticallyincreased. © 2008 Macmillan Publishers Limited. All rights reserve
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.optik.1optik.experi

Experimental generation of amplitude squeezed vector beams - Chille, Vanessa; Berg-Johansen, Stefan; Semmler, Marion; Banzer, Peter; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph (Optics Express, 2016)
We present an experimental method for the generation of amplitude squeezed high-order vector beams. The light is modified twice by a spatial light modulator such that the vector beam is created by means of a collinear interferometric technique. A major advantage of this approach is that it avoids systematic losses, which are detrimental as they cause decoherence in continuous-variable quantum systems. The utilisation of a spatial light modulator (SLM) gives the flexibility to switch between arbitrary mode orders. The conversion efficiency with our setup is only limited by the efficiency of the SLM. We show the experimental generation of Laguerre-Gauss (LG) modes with radial indices 0 or 1 and azimuthal indices up to 3 with complex polarization structures and a quantum noise reduction up to -0.9dB±0.1dB. The corresponding polarization structures are studied in detail by measuring the spatial distribution of the Stokes parameters.
CRIS-Team Scopus Importer:2022-06-05

Experiment towards continuous-variable entanglement swapping: Highly correlated four-partite quantum state - Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Heersink, Joel; Brownnutt, Michael; Silberhorn, Christine; Pan, Quing; van Loock, Peter; Korolkova, Natalia; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2003)
We present a protocol for performing entanglement swapping with intense pulsed beams. In a first step, the generation of amplitude correlations between two systems that have never interacted directly is demonstrated. This is verified in direct detection with electronic modulation of the detected photocurrents. The measured correlations are better than expected from a classical reconstruction scheme. In an entanglement swapping process, a four-partite entangled state is generated. We prove experimentally that the amplitudes of the four optical modes are quantum correlated 3 dB below shot noise, which is consistent with the presence of genuine four-party entanglement.<br

Extreme thermodynamics in nanolitre volumes through stimulated Brillouin–Mandelstam scattering - Geilen, Andreas; Popp, Alexandra; Das, Debayan; Junaid, Saher; Poulton, Christopher G.; Chemnitz, Mario; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (Nature Physics, 2023)
Examining the physical properties of materials—particularly of toxic liquids—under a wide range of thermodynamic states is a challenging problem due to the extreme conditions the material has to experience. Such temperature and pressure regimes, which result in a change in the refractive index and sound velocity, can be accessed by optoacoustic interactions such as Brillouin–Mandelstam scattering. Here we demonstrate the Brillouin–Mandelstam measurements of nanolitre volumes of liquids in extreme thermodynamic regimes. This is enabled by a fully sealed liquid-core optical fibre containing carbon disulfide. Within this waveguide, which exhibits tight optoacoustic confinement and a high Brillouin gain, we are able to conduct spatially resolved measurements of the local Brillouin response, giving us access to a resolved image of the temperature and pressure values along the liquid channel. We measure the material properties of the liquid core at very large positive pressures (above 1,000 bar) and substantial negative pressures (below –300 bar), as well as explore the isobaric and isochoric regimes. The extensive thermodynamic control allows the tunability of the Brillouin frequency shift of more than 40% using only minute volumes of liquid.
CRIS-Team Scopus Importer:2023-10-06

Fading channel estimation for free-space continuous-variable secure quantum communication - Ruppert, Laszlo; Peuntinger, Christian; Heim, Bettina; Günthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique Alexander; Leuchs, Gerd; Filip, Radim; Marquardt, Christoph (New Journal of Physics, 2019)
We investigate estimation of fluctuating channels and its effect on security of continuous-variable quantum key distribution. We propose a novel estimation scheme which is based on the clusterization of the estimated transmittance data. We show that uncertainty about whether the transmittance is fixed or not results in a lower key rate. However, if the total number of measurements is large, one can obtain using our method a key rate similar to the non-fluctuating channel even for highly fluctuating channels. We also verify our theoretical assumptions using experimental data from an atmospheric quantum channel. Our method is therefore promising for secure quantum communication over strongly fluctuating turbulent atmospheric channels.
CRIS-Team WoS Importer:2020-03-06

Feasibility of squeezing detection over satellite links - Muller, Christian R.; Seshadreesan, Kaushik P.; Leuchs, Gerd; Marquardt, Christoph (2017 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2017, 2018)
Quantum squeezing is the nonlinear quantum mechanical effect by which the Heisenberg uncertainty in one observable can be reduced below the shot noise level at the expense of increased uncertainty in its conjugate observable. We study the detection of optical quadrature squeezing via homodyne detection in satellite links. The propagation of the quantum states over large distances and through a varying gravitational potential offers the possibility to test the fundamental laws of physics at the interface of quantum mechanics and general relativity. We model the task as a binary hypothesis testing problem where the null hypothesis corresponds to the vacuum state and the alternative hypothesis corresponds to the squeezed state. Using the Chernoff bound, we derive the number of individual measurements required to limit the average error probabilities to a given value.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Continuous-variables; Homodyne detection; Optical satellite communication; Quadrature squeezing

Fiber Solitons—Quantum Interferometry and Entanglement - Leuchs, Gerd; Silberhorn, Christine; Glöckl, Oliver; Marquardt, Christoph; Korolkova, Natalia (Quantum Electronics and Laser Science Conference 2002, 2002)
The study of quantum properties of soliton pulses in fibers spans the full range from basic research to applications. New developments in high precision quantum interferometry and quantum communications will be reported as well as novel aspects of the range limit due to losses.<br

Four-state discrimination scheme beyond the heterodyne limit - Müller, Christian R.; Usuga, Mario A.; Wittmann, Christoffer; Takeoka, Masahiro; Marquardt, Christoph; Andersen, Ulrik L.; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We propose and experimentally demonstrate a hybrid discrimination scheme for the quadrature phase shift keying protocol, which outperforms heterodyne detection for any signal power. The discrimination is composed of a quadrature measurement, feed forward and photon detection. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Free-space propagation of high-dimensional structured optical fields in an urban environment - Lavery, Martin P. J.; Peuntinger, Christian; Günthner, Kevin; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Science Advances, 2017)
Spatially structured optical fields have been used to enhance the functionality of a wide variety of systems that use light for sensing or information transfer. As higher-dimensional modes become a solution of choice in optical systems, it is important to develop channel models that suitably predict the effect of atmospheric turbulence on these modes. We investigate the propagation of a set of orthogonal spatial modes across a free-space channel between two buildings separated by 1.6 km. Given the circular geometry of a common optical lens, the orthogonal mode set we choose to implement is that described by the Laguerre-Gaussian (LG) field equations. Our study focuses on the preservation of phase purity, which is vital for spatial multiplexing and any system requiring full quantum-state tomography. We present experimental data for the modal degradation in a real urban environment and draw a comparison to recognized theoretical predictions of the link. Our findings indicate that adaptations to channel models are required to simulate the effects of atmospheric turbulence placed on high-dimensional structured modes that propagate over a long distance. Our study indicates that with mitigation of vortex splitting, potentially through precorrection techniques, one could overcome the challenges in a real point-to-point free-space channel in an urban environment.
CRIS-Team Scopus Importer:2022-06-05

Free space quantum communication using continuous polarization variables - Heim, Bettina; Peuntinger, Christian; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
We experimentally investigate atmospheric influences on quantum communication using continuous polarization variables. Signal and local oscillator are combined in one spatial mode, which leads to excellent interference at the homodyne detection. Phase fluctuations are thus auto-compensated. © 2011 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Free-space quantum links under diverse weather conditions - Vasylyev, Dmytro Yu.; Semenov, A. A.; Vogel, W.; Guenthner, K.; Thurn, Andreas; Bayraktar, O.; Marquardt, Christoph (Physical Review A, 2017)
Free-space optical communication links are promising channels for establishing secure quantum communication. Here we study the transmission of nonclassical light through a turbulent atmospheric link under diverse weather conditions, including rain or haze. To include these effects, the theory of light transmission through atmospheric links in the elliptic-beam approximation presented by Vasylyev et al. [D. Vasylyev, Phys. Rev. Lett. 117, 090501 (2016)PRLTAO0031-900710.1103/PhysRevLett.117.090501] is further generalized. It is demonstrated, with good agreement between theory and experiment, that low-intensity rain merely contributes additional deterministic losses, whereas haze also introduces additional beam deformations of the transmitted light. Based on these results, we study theoretically the transmission of quadrature squeezing and Gaussian entanglement under these weather conditions.
CRIS-Team Scopus Importer:2022-06-05

Free-Space Quantum Signatures Using Heterodyne Measurements - Croal, Callum; Peuntinger, Christian; Heim, Bettina; Khan, Imran; Marquardt, Christoph; Leuchs, Gerd; Wallden, Petros; Andersson, Erika; Korolkova, Natalia (Physical Review Letters, 2016)
Digital signatures guarantee the authorship of electronic communications. Currently used "classical" signature schemes rely on unproven computational assumptions for security, while quantum signatures rely only on the laws of quantum mechanics to sign a classical message. Previous quantum signature schemes have used unambiguous quantum measurements. Such measurements, however, sometimes give no result, reducing the efficiency of the protocol. Here, we instead use heterodyne detection, which always gives a result, although there is always some uncertainty. We experimentally demonstrate feasibility in a real environment by distributing signature states through a noisy 1.6 km free-space channel. Our results show that continuous-variable heterodyne detection improves the signature rate for this type of scheme and therefore represents an interesting direction in the search for practical quantum signature schemes. For transmission values ranging from 100% to 10%, but otherwise assuming an ideal implementation with no other imperfections, the signature length is shorter by a factor of 2 to 10. As compared with previous relevant experimental realizations, the signature length in this implementation is several orders of magnitude shorter.
CRIS-Team Scopus Importer:2022-06-05

Frequency tuning of single photons from a whispering-gallery mode resonator to MHz-wide transitions - Schunk, G.; Vogl, Ulrich; Sedlmeir, F.; Strekalov, D. V.; Otterpohl, A.; Averchenko, V.; Schwefel, H. G. L.; Leuchs, Gerd; Marquardt, Christoph (Journal of Modern Optics, 2016)
Quantum repeaters rely on interfacing flying qubits with quantum memories. The most common implementations include a narrowband single photon matched in bandwidth and central frequency to an atomic system. Previously, we demonstrated the compatibility of our versatile source of heralded single photons, which is based on parametric down-conversion in a triply resonant whispering-gallery mode resonator, with alkaline transitions [Schunk et al., Optica 2015,2, 773]. In this paper, we analyse our source in terms of phase matching, available wavelength-tuning mechanisms and applications to narrowband atomic systems. We resonantly address the D1 transitions of caesium and rubidium with this optical parametric oscillator pumped above its oscillation threshold. Below threshold, the efficient coupling of single photons to atomic transitions heralded by single telecom-band photons is demonstrated. Finally, we present an accurate analytical description of our observations. Providing the demonstrated flexibility in connecting various atomic transitions with telecom wavelengths, we show a promising approach to realize an essential building block for quantum repeaters.
CRIS-Team Scopus Importer:2022-06-05
Keywords: (270.5565) Quantum communications; (300.6210) Spectroscopy; 190.4970 Parametric oscillators and amplifiers; atomic; OCIS: (270.0270) Quantum optics

Fundamentally secure data with the help of quantum key distribution on CubeSats - Haber, Roland; Scharnagl, Julian; Schilling, Klaus; Weinfurter, Harald; Marquardt, Christoph; Moll, Florian; Grünefeld, Matthias; Freiwang, Peter; Rosenfeld, Wenjamin; Bayraktar, Ömer; Rödiger, Benjamin; Schmidt, Christopher (Proceedings of the International Astronautical Congress, IAC, 2019)
With the uprise of worldwide satellite communication networks, data security is a critical issue. This issue is being addressed in the QUBE project, which proposes a CubeSat for quantum cryptography experiments. The satellite and its subsystems are currently being developed and will be used for the downlink of individual photons, or strongly attenuated light pulses, containing encoded quantum information, which can then be employed for the exchange of encryption keys. The launch of the 3U Nanosatellite is planned for early 2020. It will be built using the UNISEC-Europe standard, which has demonstrated to be able to provide a robust structure for increased reliability in CubeSat missions. In addition to state-of-the-art reaction wheels for precision pointing, the satellite will be bringing the OSIRIS optical downlink system from DLR as well as two dedicated payloads for testing components required for quantum key distribution. A sequence of numbers will be created by a miniaturized quantum random number generator (QRNG), which will be used to set the quantum states of the light pulses. These pulses will then be downlinked to the optical ground station (OGS) at DLR in Oberpfaffenhofen, Germany. The ground station is also equipped with the corresponding components for receiving individual quantum states. In addition, the random numbers will be made available via an RF downlink. The photon states received by the optical ground station will then be compared to the previously generated numbers. Due to the underlying quantum mechanics, any attempt of reading the quantum states will alter them, which makes interceptions easily detectable. These quantum key distribution experiments will evaluate whether secure communication links are possible even on a CubeSat scale. A major challenge for building the proposed CubeSat is the attitude determination and control system that will provide precise pointing. This work will outline detailed mission requirements as well as the chosen subsystems for tackling these challenges in order to achieve a successful mission and prepare for future data security.
CRIS-Team Scopus Importer:2022-06-05
Keywords: CubeSat; QKD; QRNG; Quantum Encryption

GAWBS noise reduction in microstructured fibers - Elser, Dominique Alexander; Korn, Alexander; Lorenz, Stefan; Glöckl, Oliver; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (2005 European Quantum Electronics Conference, EQEC '05, 2005)
Guided Acoustic Wave Brillouin Scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. We experimentally demonstrate the reduction of GAWBS noise in microstructured fibers in comparison with standard fibers. © 2005 IEEE.
Created from Fastlane, Scopus look-up

Generation and applications of quantum engineered optical soliton pulses - Leuchs, Gerd; Andersen, Ulrik Lund; Glöckl, Oliver; Marquardt, Christoph; Heersink, Joel; Lorenz, Stefan (2005 European Quantum Electronics Conference, EQEC '05, 2005)
We describe various quantum protocols, all of which can be described by Bogoliubov transformations. Furthermore, a scheme by which correlated sidebands of a single spatial mode can be separated into two spatial modes is outlined. © 2005 IEEE.
Created from Fastlane, Scopus look-up

Generation of non-classical light via selfinduced transparency in mercury-filled hollow core photonic crystal fibers - Vogl, Ulrich; Sedlmeir, Florian; Joly, Nicolas Y.; Marquardt, Christoph; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2016)
We successfully demonstrate squeezing of nanosecond pulses via self-induced transparency in a system of mercury vapor confined in a hollow core kagomé-style fiber.
CRIS-Team Scopus Importer:2022-06-05

Geometric Spin Hall Effect of Light at polarizing interfaces - Korger, J.; Aiello, Andrea; Gabriel, C.; Banzer, Peter; Kolb, T.; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2011)
The geometric Spin Hall Effect of Light (geometric SHEL) amounts to a polarization-dependent positional shift when a light beam is observed from a reference frame tilted with respect to its direction of propagation. Motivated by this intriguing phenomenon, the energy density of the light beam is decomposed into its Cartesian components in the tilted reference frame. This illustrates the occurrence of the characteristic shift and the significance of the effective response function of the detector. We introduce the concept of a tilted polarizing interface and provide a scheme for its experimental implementation. A light beam passing through such an interface undergoes a shift resembling the original geometric SHEL in a tilted reference frame. This displacement is generated at the polarizer and its occurrence does not depend on the properties of the detection system.We give explicit results for this novel type of geometric SHEL and show that at grazing incidence this effect amounts to a displacement of multiple wavelengths, a shift larger than the one introduced by Goos-Hänchen and Imbert-Fedorov effects. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-05

GHz kinematic sensing with classically entangled beams of light - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, M.; Giacobino, E.; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2021-06-29

Goals and feasibility of the Deep Space Quantum Link - Mazzarella, Luca; Mohageg, Makan; Strekalov, Dmitry V.; Zhai, Aileen; Israelsson, Ulf; Matsko, Andrey; Yu, Nan; Anastopoulos, Charis; Carpenter, Bradley; Gallicchio, Jason; Hu, Bei Lok; Jennewein, Thomas; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
In this article, we review the proposed experiments for the Deep Space Quantum Link (DSQL) mission concept aiming to probe gravitational effects on quantum optical systems. Quantum theory and general relativity are the two most successful frameworks we have to describe the universe. These theories have been validated through experimental confirmations in their domains of application— the macroscopic domain for relativity, and the microscopic domain for quantum theory. To date, laboratory experiments conducted in a regime where both theories manifest measurable effects on photons are limited. Satellite platforms enable the transmission of quantum states of light between different inertial frames and over distances impossible to emulate in the laboratory. The DSQL concept proposes simultaneous tests of quantum mechanics and general relativity enabled by quantum optical links to one or more spacecrafts.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Foundational quantum theory; General relativity; Quantum optics

Guided acoustic wave Brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Wittmann, Christoffer; Andersen, Ulrik Lund; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Journal of Physics: Conference Series, 2007)
In silica glass fibers, thermally excited acoustic phonons scatter light into the beam propagating in the forward direction. At acoustic frequencies up to several hundreds of megahertz, the wave vectors of the phonons interacting with the light propagate essentially transversally to the fiber axis. This effect is known as Guided Acoustic Wave Brillouin Scattering (GAWBS) and leads to phase and polarization noise in the guided light. For fiber-based quantum optics experiments, this excess noise is a major limitation. In Photonic Crystal Fibers (PCFs), light is guided by a microstructure simultaneously acting as a 2D transversal phononic crystal which modifies the acoustic noise spectrum. We demonstrate a GAWBS-noise reduction in commercially available PCFs. This gives rise to the prospect of fiber-based quantum optic devices exhibiting less excess noise, thus resulting in higher quantum state purity. Further improvement can be achieved by tailoring the photonic microstructure such that a reduction of phonon noise by design is achieved. © 2007 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up

High-dimensional intracity quantum cryptography with structured photons - Sit, Alicia; Bouchard, Frederic; Fickler, Robert; Gagnon-Bischoff, Jeremie; Larocque, Hugo; Heshami, Khabat; Elser, Dominique; Peuntinger, Christian; Günthner, Kevin; Heim, Bettina; Marquardt, Christoph; Leuchs, Gerd; et al. (Optica, 2017)
Quantum key distribution (QKD) promises information-theoretically secure communication and is already on the verge of commercialization. The next step will be to implement high-dimensional protocols in order to improve noise resistance and increase the data rate. Hitherto, no experimental verification of high-dimensional QKD in the single-photon regime has been conducted outside of the laboratory. Here, we report the realization of such a single-photon QKD system in a turbulent free-space link of 0.3 km over the city of Ottawa, taking advantage of both the spin and orbital angular momentum photonic degrees of freedom. This combination of optical angular momenta allows us to create a 4-dimensional quantum state; wherein, using a high-dimensional BB84 protocol, a quantum bit error rate of 11% was attained with a corresponding secret key rate of 0.65 bits per sifted photon. In comparison, an error rate of 5% with a secret key rate of 0.43 bits per sifted photon is achieved for the case of 2-dimensional structured photons. We thus demonstrate that, even through moderate turbulence without active wavefront correction, high-dimensional photon states are advantageous for securely transmitting more information. This opens the way for intracity high-dimensional quantum communications under realistic conditions.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Free-space optical communication; Optical vortices; Quantum cryptography

Highly efficient generation of narrow-band single-mode photon pairs from a whispering gallery mode resonator - Förtsch, Michael; Schunk, Gerhard; Josef Fürst; Strekalov, Dmitry; Gerrits, Thomas; Stevens J., Martin J.; Sedlmeir, Florian; Schwefel G.L., Harald G.L.; Nam, Sae Woo; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2014)
We present a highly efficient narrow-band pair-photon source based on a crystalline whispering gallery mode resonator, which emits photons in exactly one spatiotemporal mode. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Highly efficient generation of single-mode photon pairs from a crystalline whispering-gallery-mode resonator source - Foertsch, Michael; Schunk, Gerhard; Fuerst, Josef U.; Strekalov, Dmitry; Gerrits, Thomas; Stevens, Martin J.; Sedlmeir, Florian; Schwefel, Harald G. L.; Nam, Sae Woo; Leuchs, Gerd; Marquardt, Christoph (Physical Review A - Atomic, Molecular, and Optical Physics, 2015)
We report a highly efficient source of narrow-band photon pairs based on parametric down-conversion in a crystalline whispering-gallery-mode resonator. Remarkably, each photon of a pair is detected in a single spatial and temporal mode, as witnessed by Glauber's autocorrelation function. We explore the phase-matching conditions in spherical geometries, and determine the requirements for single-mode operation. Understanding these conditions has allowed us to experimentally demonstrate a single-mode pair-detection efficiency of 1.13×106 pairs/s per mW pump power per 26.8 MHz bandwidth.
CRIS-Team Scopus Importer:2022-06-05

Identifying modes of large whispering-gallery mode resonators from the spectrum and emission pattern - Schunk, Gerhard; Fuerst, Josef U.; Foertsch, Michael; Strekalov, Dmitry V.; Vogl, Ulrich; Sedlmeir, Florian; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (Optics Express, 2014)
Identifying the mode numbers in whispering-gallery mode resonators (WGMRs) is important for tailoring them to experimental needs. Here we report on a novel experimental mode analysis technique based on the combination of frequency analysis and far-field imaging for high mode numbers of large WGMRs. The radial mode numbers q and the angular mode numbers p = l-m are identified and labeled via far-field imaging. The polar mode numbers l are determined unambiguously by fitting the frequency differences between individual whispering gallery modes (WGMs). This allows for the accurate determination of the geometry and the refractive index at different temperatures of the WGMR. For future applications in classical and quantum optics, this mode analysis enables one to control the narrow-band phase-matching conditions in nonlinear processes such as second-harmonic generation or parametric down-conversion.
CRIS-Team Scopus Importer:2022-06-05

Indistinguishable MHz-narrow heralded photon pairs from a whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph (APL Photonics, 2025)
The Hong-Ou-Mandel interference plays a vital role in many quantum optical applications where indistinguishability of two photons is important. Such photon pairs are commonly generated as the signal and idler in the polarization-degenerate spontaneous parametric downconversion (SPDC). To scale this approach to a larger number of photons, we demonstrate how two independent signal photons radiated into different spatial modes can be rendered conditionally indistinguishable by a heralding measurement performed on their respective idlers. We use the SPDC in a whispering gallery resonator, which is already proven to be versatile sources of quantum states. Its extreme conversion efficiency allowed us to perform our measurements with only 50 nW of in-coupled pump power in each propagation direction. The Hong-Ou-Mandel interference of two counterpropagating signal photons manifested itself in the fourfold coincidence rate, where the detection of two idler photons heralds a pair of signal photons with a desired temporal overlap. We achieved the Hong-Ou-Mandel dip contrast of 74% ± 5%. Importantly, the optical bandwidth of all involved photons is of the order of a MHz and is continuously tunable. This, on the one hand, makes it possible to achieve the necessary temporal measurement resolution with standard electronics and, on the other hand, creates a quantum state source compatible with other candidates for qubit implementation, such as optical transitions in solid-state or vaporous systems. We also discuss the possibility of generating photon pairs with similar temporal modes from two different whispering gallery resonators.
CRIS-Team Scopus Importer:2025-05-30

Inducing a detector efficiency mismatch to hack a commercial quantum key distribution system - Jain, N.; Lydersen, L.; Wittmann, C.; Wiechers, C.; Elser, D.; Marquardt, Christoph; Makarov, V.; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Quantum key distribution (QKD) is poised to be the first widespread implementation of quantum communication. In principle, it offers unconditional security: an eavesdropper introduces errors and thus cannot remain concealed from the legitimate parties. However, in practical implementations the actual security depends on a host of technological and protocol-operational components. Eve could exploit imperfections in Alice's or Bob's equipment (such as source or detectors) remotely, or vulnerabilities in the actual implementation of the abstract QKD protocol. Several such attacks have been proposed [1,2], and various proof-of-principle demonstrations on commercial QKD devices have been performed in recent years [3-5]. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-06-05

Integrated Photonics for Quantum Communication on a Cubesat - Pudelko, Jonas; Bayraktar, Ömer; Khan, Imran; Boxleitner, Winfried; Petscharnig, Stefan; Pacher, Christoph; Leuchs, Gerd; Marquardt, Christoph (2023 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC), 2023)
The limited range of quantum key distribution (QKD) in fiber based systems led to several projects aiming for the development of a satellite based QKD infrastructure, like the conduction of quantum limited measurements from a geostationary satellite [1] or the MICIUS mission, which impressively demonstrated QKD on a global scale [2]. However, due to the high costs of satellite launches the profitability of commercial systems would benefit dramatically from further reduction in size, weight and power. Photonic integration [3] addresses these points by allowing the integration of all optical components of a QKD system on a photonic integrated circuit (PIC). In this work, we are going to demonstrate building blocks for quantum communication from space based on photonic integration technology by building a payload for the CubeSat mission QUBE [4] consisting of an integrated sender for weak coherent states as well as an integrated Quantum Random Number Generator (QRNG).<br

Interfacing transitions of different alkali atoms and telecom bands using one narrowband photon pair source - Schunk, Gerhard; Vogl, Ulrich; Strekalov, Dmitry V.; Förtsch, Michael; Sedlmeir, Florian; Schwefel, Harald; Göbelt, Manuela; Christiansen, Silke; Leuchs, Gerd; Marquardt, Christoph (Optica, 2015)
Quantum information technology strongly relies on the coupling of optical photons with narrowband quantum systems, such as quantum dots, color centers, and atomic systems. This coupling requires matching the optical wavelength and bandwidth to the desired system, which presents a considerable problem for most available sources of quantum light. Here we demonstrate the coupling of alkali dipole transitions with a tunable source of photon pairs. Our source is based on spontaneous parametric downconversion in a triply resonant whispering gallery mode resonator. For this, we have developed novel wavelength-tuning mechanisms that allow a coarse tuning to either the cesium or rubidium wavelength, with subsequent continuous fine-tuning to the desired transition. As a demonstration of the functionality of the source, we performed a heralded single-photon measurement of the atomic decay. We present a major advance in controlling the spontaneous downconversion process, which makes our bright source of heralded single photons now compatible with a plethora of narrowband resonant system
Keywords: Atomic; Quantum communications; Quantum optics; Spectroscopy

Interference of two intense entanglement sources: entanglement swapping and multi-partite entanglement - Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Heersink, Joel; Pan, Quing; van Loock, Peter; Korolkova, Natalia; Leuchs, Gerd (2003 European Quantum Electronics Conference. EQEC 2003, 2003)
Progress of entanglement swapping experiment is reported. Four highly correlated modes are created by the interference of two entangled systems. As calculations show, there are strong hints that the state is indeed multi-partite entangled.<br
Keywords: Quantum entanglement; Physics; Hilbert space; Telecommunication standards; Cryptography; Teleportation

Intracavity Squeezing Can Enhance Quantum-Limited Optomechanical Position Detection through Deamplification - Peano, Vittorio; Schwefel, Harald; Marquardt, Christoph; Marquardt, Florian (Physical Review Letters, 2015)
It has been predicted and experimentally demonstrated that by injecting squeezed light into an optomechanical device, it is possible to enhance the precision of a position measurement. Here, we present a fundamentally different approach where the squeezing is created directly inside the cavity by a nonlinear medium. Counterintuitively, the enhancement of the signal-to-noise ratio works by deamplifying precisely the quadrature that is sensitive to the mechanical motion without losing quantum information. This enhancement works for systems with a weak optomechanical coupling and/or strong mechanical damping. This can allow for larger mechanical bandwidth of quantum-limited detectors based on optomechanical devices. Our approach can be straightforwardly extended to quantum nondemolition qubit detection.
CRIS-Team Scopus Importer:2022-06-05

Investigation of noise sources down to the shot-noise limit in Yb-doped fiber amplifers for TMI investigations - Popp, Alexandra; Bock, Victor; Sedlmeir, Florian; Muller, Christian R.; Haarlammert, Nicoletta; Schreiber, Thomas; Marquardt, Christoph; Tunnermann, Andreas; Leuchs, Gerd (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Ytterbium-doped fiber laser amplifiers are known for their high single-pass gain and average powers up to the kilowatt range, while maintaining single-mode output. An upper limitation for the achievable output power is given by transverse mode instabilities (TMI). Due to the interference with higher order modes that create a thermally induced long period grating, chaotic power transfer happens above a certain threshold, which degrades the beam quality. It has been shown that this effect can be influenced by manipulating the grating strength itself. It has also been shown that a certain phase relation of the grating to the guided modes is necessary to efficiently transfer power or hinder the effect by phase disturbance [1]. A natural phase disturbance is given by noise, which is introduced by the pump or seed source in a fiber amplifer. In this contribution, we experimentally investigate the amount of intensity noise in a fiber-pre-amplifer, which is typically used in kW experiments and relate it to the fundamental shot noise limit (SNL). In the experiments, we used a single-frequency external cavity diode laser as a low noise source and amplify it by 30 dB from 10 mW to an output power of 10 W. This is a typical pre-amplifier configuration, before such sources can be amplified to the kW level. The fiber amplifier is a double-clad fiber with a 10/125 μm geometry, pumped by a wavelength stabilized pump diode at 976 nm via a monolithic pump coupler. In order to prevent stimulated Brillouin scattering, the seed laser is phase modulated by a combination of a sinusoid and white noise and thus broadened to 50 GHz linewidth. The noise measurements are done by balanced self-homodyne detection including optimized photodiode readout circuits spanning different frequency ranges. The recorded spectra are given in Fig. 1. The SNL was verified through an attenuation measurement for the subtracted detector signals. Finally, the measured excess noise values are fitted by their corresponding second-order polynomial power dependency and extrapolated to the full power of the amplifier. The seed source, phase modulator and fiber amplifier have been characterized in this setup separately to investigate their contributions. For the fiber amplifier, both co- and counter-pumping configuration, are analysed. Due to detector limitations, all given spectra are measured at an optical power in the mW regime corresponding to approx. 30 dB of attenuation in the amplifiers.
CRIS-Team Scopus Importer:2019-11-15

Kerr-effect induced correlations of optical fiber solitons and the impact of phase control - Leuchs, Gerd; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Heersink, Joel; Korolkova, Natalia (Frontiers in Optics 2003, 2003)
Experiments are reported in which the quantum properties of intense optical pulses at 1.5 micrometer are controlled via their non-linear interaction with the optical fiber. Intense light pulses may exhibit non-classical features such as entanglement with application in quantum communication. The role of phase control will be discussed.<br

Laser based bi-directional Gbit ground links with the Tesat transportable adaptive optical ground station - Heine, Frank; Saucke, Karen; Troendle, Daniel; Motzigemba, Matthias; Bischl, Hermann; Elser, Dominique; Marquardt, Christoph; Henniger, Hennes; Meyer, Rolf; Richter, Ines; Sodnik, Zoran (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Optical ground stations can be an alternative to radio frequency based transmit (forward) and receive (return) systems for data relay services and other applications including direct to earth optical communications from low earth orbit spacecrafts, deep space receivers, space based quantum key distribution systems and Tbps capacity feeder links to geostationary spacecrafts. The Tesat Transportable Adaptive Optical Ground Station is operational since September 2015 at the European Space Agency site in Tenerife, Spain. This paper reports about the results of the 2016 experimental campaigns including the characterization of the optical channel from Tenerife for an optimized coding scheme, the performance of the T-AOGS under different atmospheric conditions and the first successful measurements of the suitability of the Alphasat LCT optical downlink performance for future continuous variable quantum key distribution systems.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Atmospheric dynamics; Coding; Forward error correction; Laser Communication; Optical ground station

Localized temperature and pressure measurements inside CS2-filled fiber using stimulated Brillouin scattering - Popp, Alexandra; Geilen, Andreas; Walter, Daniel; Chemnitz, Mario; Junaid, Saher; Poulton, Christopher G.; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Liquid-core fibers are a versatile platform for nonlinear light-matter interactions, combining highly nonlinear materials like carbon disulfide (CS 2 ) or nitrobenzene with the confinement and long interaction length of optical fibers. While there is only minor influence of strain inside the fiber core due to the liquid phase, pressure effects have a dominant role depending on the thermodynamic regime and filling of the fiber core [1]. In our experiments we use Brillouin Optical Correlation Domain Analysis (BOCDA) to create a localized Brillouin response [2]. Due to the associated refractive index change, this response is strain, pressure and temperature dependent. While the discrimination of strain and temperature effects in silica fibers is complicated due to the combined Brillouin response [3] , CS 2 filled fibers have the advantage of thermo- and piezo-optical coefficients with different signs. While the thermo-optic coefficient is negative, resulting in a downshifted acoustic response for higher temperature, the piezo-optic coefficient is positive, resulting in an upshifted Brillouin frequency for increased pressure. To investigate the response of the CS 2 , we heated different parts of the 60cm liquid-core fiber on a hotplate up to a temperature of 135 C while measuring the distributed Brillouin response with a resolution of 4cm.
CRIS-Team Scopus Importer:2021-10-29

Localizing Eavesdroppers Inside a Quantum Channel Using Stimulated Brillouin Scattering - Popp, Alexandra; Stiller, Birgit; Marquardt, Christoph (2023 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC), 2023)
While modern communication systems pose a high standard of security using state-of-the-art encryption techniques based on computational hardness problems, quantum key distribution (QKD) offers a unique advantage using the laws of quantum mechanics. A secret key is shared between two parties, using quantum states of light over a quantum channel. Due to the quantum nature of the states, any interception or other way of eavesdropping will manifest in the distortion of the quantum state resulting in a change of accessible parameters. Whenever such a change of parameters is noticed, the shared key is marked unsecure and hashed down largely or, in the worst case, discarded.<br
Keywords: Quantum computing; Quantum channels; Europe; Quantum state; Distortion; Quantum key distribution; Encryption

Long distance free-space propagation of light carrying orbital angular momentum - Lavery, Martin P.J.; Peuntinger, Christian; Günthner, Kevin; Bauer, Thomas; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2016)
We present analysis of the technical challenges facing deployment of longdistance free-space links employing orbital angular momentum multiplexing. Our analysis indicates atmospheric mitigation techniques, and modal purity are important consideration for system design.
CRIS-Team Scopus Importer:2022-06-05

Low-threshold optical parametric oscillations in a whispering gallery mode resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique Alexander; Aiello, Andrea; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2010)
In whispering gallery mode (WGM) resonator light is guided by continuous total internal reflection along a curved surface. Fabricating such resonators from an optically nonlinear material one takes advantage of their exceptionally high quality factors and small mode volumes to achieve extremely efficient optical frequency conversion. Our analysis of the phase-matching conditions for optical parametric down-conversion (PDC) in a spherical WGM resonator shows their direct relation to the sum rules for photons' angular momenta and predicts a very low parametric oscillation threshold. We realized such an optical parametric oscillator (OPO) based on naturally phase-matched PDC in lithium niobate. We demonstrated a single-mode, strongly nondegenerate OPO with a threshold of 6.7μW and linewidth under 10 MHz. This work demonstrates the remarkable capabilities of WGM-based OPOs. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Low-threshold optical parametric oscillations in a whispering gallery mode resonator - Fürst, J. U.; Strekalov, D. V.; Elser, D.; Aiello, A.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Whispering gallery mode (WGM) resonators feature strong optical confinement, small mode volume, and offer tunable coupling to an external optical field. Fabricating WGM resonators from lithium niobate one can take advantage of these properties to achieve very strong optical nonlinear response, e. g. parametric downconversion (PDC). This process offers a highly wavelength tunable light source and is used as a state of the art source for nonclassical light. Driving PDC in cavities, also referred to as an optical parametric oscillator (OPO), provides efficient wavelength conversion. Thus, it is intruiging to investigate PDC in a WGM resonator, although phase matching conditions become involved in spherical geometry. In the process of higher harmonic generation, quasi phase-matching has already been demonstrated in a lithium niobate WGM cavity [1, 2], showing the potential of these resonators. Here we present a highly efficient OPO with a WGM resonator using natural temperature phase matching, where the individual optical fields have narrow optical linewidth [3]. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-06-05

M-ary phase shift keying receiver beating the standard quantum limit for any signal power - Müller, Christian R.; Leven, Andreas; Bülow, Henning; Schmalen, Laurent; Leuchs, Gerd; Marquardt, Christoph (European Conference on Optical Communication, ECOC, 2014)
We analyze a novel quantum receiver for M-ary phase-shift keyed signals that outperforms the standard quantum limit for any signal power. We provide a detailed analysis of its robustness against realistic imperfections and discuss the achievable mutual information.
CRIS-Team Scopus Importer:2022-06-05

Measuring higher-order photon correlations of faint quantum light: A short review - Laiho, K.; Dirmeier, T.; Schmidt, Marco; Reitzenstein, S.; Marquardt, Christoph (Physics Letters A, 2022)
Normalized correlation functions provide expedient means for determining the photon-number properties of light. These higher-order moments, also called the normalized factorial moments of photon number, can be utilized both in the fast state classification and in-depth state characterization. Further, non-classicality criteria have been derived based on their properties. Luckily, the measurement of the normalized higher-order moments is often loss-independent making their observation with lossy optical setups and imperfect detectors experimentally appealing. The normalized higher-order moments can for example be extracted from the photon-number distribution measured with a true photon-number-resolving detector or accessed directly via manifold coincidence counting in the spirit of the Hanbury Brown and Twiss experiment. Alternatively, they can be inferred via homodyne detection. Here, we provide an overview of different kind of state classification and characterization tasks that take use of normalized higher-order moments and consider different aspects in measuring them with free-traveling light. (C)& nbsp;2022 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2022-05-20

Microsphere kinematics from the polarization of tightly focused nonseparable light - Berg-Johansen, Stefan; Neugebauer, Martin; Aiello, Andrea; Leuchs, Gerd; Banzer, Peter; Marquardt, Christoph (Optics Express, 2021)
Recently, it was shown that vector beams can be utilized for fast kinematic sensing via measurements of their global polarization state [Optica 2, 864 (2015)]. The method relies on correlations between the spatial and polarization degrees of freedom of the illuminating field which result from its nonseparable mode structure. Here, we extend the method to the nonparaxial regime. We study experimentally and theoretically the far-field polarization state generated by the scattering of a dielectric microsphere in a tightly focused vector beam as a function of the particle position. Using polarization measurements only, we demonstrate position sensing of a Mie particle in three dimensions. Our work extends the concept of back focal plane interferometry and highlights the potential of polarization analysis in optical tweezers employing structured light.
CRIS-Team Scopus Importer:2021-04-30

Mode-hop-free tunable optical parametric oscillator utilizing a whispering gallery mode resonator - Förtsch, Michael; Schunk, Gerhard; Sedlmeir, Florian; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Schwefel, Harald G.L.; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We report on a compact and stable optical parametric oscillator in a whispering gallery mode resonator, that combines very low pump thresholds with versatile tunability. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Multipolar hierarchy of efficient quantum polarization measures - De La Hoz, Pablo; Klimov, A. B.; Bjork, G.; Kim, Y. -H.; Mueller, C.; Marquardt, Christoph; Leuchs, Gerd; Sanchez-Soto, L. L.; Marquardt, Christoph (Physical Review A - Atomic, Molecular, and Optical Physics, 2013)
We advocate a simple multipole expansion of the polarization density matrix. The resulting multipoles appear as successive moments of the Stokes variables and can be obtained from feasible measurements. In terms of these multipoles we construct a whole hierarchy of measures that accurately assess higher-order polarization fluctuations. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Nanobore PCF maintaining cylindrically polarized modes - Euser, T. G.; Joly, N. Y.; Gabriel, C.; Marquardt, Christoph; Zang, L. Y.; Banzer, P.; Brenn, A.; Elser, D.; Förtsch, M.; Rammler, S.; Scharrer, M.; Leuchs, Gerd; et al. (Optics InfoBase Conference Papers, 2010)
A nanoscale hole placed centrally in the core of a PCF breaks the degeneracy between radially and azimuthally polarized modes, causing a large splitting in phase velocity, group velocity and dispersion. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Naturally phase-matched second-harmonic generation in a whispering-gallery-mode resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique Alexander; Lassen, M.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2010)
We demonstrate for the first time natural phase matching for optical frequency doubling in a high-Q whispering-gallery-mode resonator made of lithium niobate. A conversion efficiency of 9% is achieved at 30μW in-coupled continuous wave pump power. The observed saturation pump power of 3.2 mW is almost 2 orders of magnitude lower than the state-of-the-art value. This suggests an application of our frequency doubler as a source of nonclassical light requiring only a low-power pump, which easily can be quantum noise limited. Our theoretical analysis of the three-wave mixing in a whispering-gallery-mode resonator provides the relative conversion efficiencies for frequency doubling in various modes. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Naturally phase matched second harmonic generation in a whispering gallery mode resonator - Fürst, Josef; Strekalov, Dmitry; Elser, Dominique Alexander; Lassen, Mikael; Andersen, Ulrik L.; Marquardt, Christoph; Leuchs, Gerd (Lasers and Electro-Optics/Quantum Electronics and Laser Science Conference: 2010 Laser Science to Photonic Applications, CLEO/QELS 2010, 2010)
We observed conversion efficiencies of 9% at 30 μW pump power in LiNbO3, as well as self-limiting effects at high powers. The continuous-wave pump at a wavelength of 1064nm and the second-harmonic feature Q > 107. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Near-infrared single-photon spectroscopy of a whispering gallery mode resonator using energy-resolving transition edge sensors - Foertsch, Michael; Gerrits, Thomas; Stevens, Martin J.; Strekalov, Dmitry; Schunk, Gerhard; Fuerst, Josef U.; Vogl, Ulrich; Sedlmeir, Florian; Schwefel, Harald G. L.; Leuchs, Gerd; Nam, Sae Woo; Marquardt, Christoph (Journal of Optics, 2015)
We demonstrate a method to perform spectroscopy of near-infrared single photons without the need of dispersive elements. This method is based on a photon energy resolving transition edge sensor and is applied for the characterization of widely wavelength tunable narrow-band single photons emitted from a crystalline whispering gallery mode resonator. We measure the emission wavelength of the generated signal and idler photons with an uncertainty of up to 2 nm.
CRIS-Team Scopus Importer:2022-06-05
Keywords: boronitrene; graphene; nonlinear optics; sum-frequency generation

Near-infrared spectroscopy on a single photon level - Fortsch, Michael; Gerrits, Thomas; Stevens, Martin J.; Furst, Josef U.; Schunk, Gerhard; Sedlmeir, Florian; Schwefel, Harald G.L.; Strekalov, Dmitry; Nam, Sae Woo; Leuchs, Gerd; Marquardt, Christoph (Pacific Rim Conference on Lasers and Electro-Optics, CLEO - Technical Digest, 2013)
We present a spectroscopy technique on the single photon level by combining a widely wavelength tunable single photon source based on a crystalline whispering gallery mode resonator with an energy resolving transition edge sensor. © 2013 IEEE.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Photonics; Optical resonators; Laser excitation; Temperature measurement; Optical frequency conversion; Energy resolution

Noise-powered probabilistic concentration of phase information - Usuga, Mario A.; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Leuchs, Gerd; Andersen, Ulrik L. (Nature Physics, 2010)
Phase-insensitive optical amplification of an unknown quantum state is known to be a fundamentally noisy operation that inevitably adds noise to the amplified state. However, this fundamental noise penalty in amplification can be circumvented by resorting to a probabilistic scheme as recently proposed and demonstrated in refs 6, 7, 8. These amplifiers are based on highly non-classical resources in a complex interferometer. Here we demonstrate a probabilistic quantum amplifier beating the fundamental quantum limit using a thermal-noise source and a photon-number-subtraction scheme. The experiment shows, surprisingly, that the addition of incoherent noise leads to a noiselessly amplified output state with a phase uncertainty below the uncertainty of the state before amplification. This amplifier might become a valuable quantum tool in future quantum metrological schemes and quantum communication protocols. © 2010 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Non-classical light generated in a whispering gallery mode parametric oscillator - Förtsch, Michael; Schunk, G.; Fürst, J. U.; Strekalov, D. V.; Aiello, A.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
We present the generation of quantum correlated twin beams in a whispering gallery mode resonator made from lithium niobate and the first direct observation of amplitude squeezing for the single parametric beams. © 2011 AOS.
CRIS-Team Scopus Importer:2022-06-05

Nonlinear and quantum optics with whispering gallery resonators - Strekalov, Dmitry V.; Marquardt, Christoph; Matsko, Andrey B.; Schwefel, Harald G. L.; Leuchs, Gerd (Journal of Optics, 2016)
Optical whispering gallery modes (WGMs) derive their name from a famous acoustic phenomenon of guiding a wave by a curved boundary observed nearly a century ago. This phenomenon has a rather general nature, equally applicable to sound and all other waves. It enables resonators of unique properties attractive both in science and engineering. Very high quality factors of optical WGM resonators persisting in a wide wavelength range spanning from radio frequencies to ultraviolet light, their small mode volume, and tunable in- and out- coupling make them exceptionally efficient for nonlinear optical applications. Nonlinear optics facilitates interaction of photons with each other and with other physical systems, and is of prime importance in quantum optics. In this paper we review numerous applications of WGM resonators in nonlinear and quantum optics. We outline the current areas of interest, summarize progress, highlight difficulties, and discuss possible future development trends in these areas.
CRIS-Team Scopus Importer:2022-06-05
Keywords: microresonators; non-classical light; optical wave mixing

Nonlinear optics in crystalline: Whispering gallery resonators - Marquardt, Christoph; Strekalov, Dmitry V.; Fürst, Josef; Förtsch, Michael; Leuchs, Gerd (Optics and Photonics News, 2013)
CRIS-Team Scopus Importer:2022-06-05

Nonlinear power dependence of the spectral properties of an optical parametric oscillator below threshold in the quantum regime - Shafiee, Golnoush; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schunk, Gerhard; Vogl, Ulrich; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (New Journal of Physics, 2020)
Photon pairs and heralded single photons, obtained from cavity-assisted parametric down conversion (PDC), play an important role in quantum communications and technology. This motivated a thorough study of the spectral and temporal properties of parametric light, both above the optical parametric oscillator (OPO) threshold, where the semiclassical approach is justified, and deeply below it, where the linear cavity approximation is applicable. The pursuit of a higher two-photon emission rate leads into an interesting intermediate regime, between above OPO threshold and very low pump power, where the OPO still operates considerably below the threshold but the nonlinear cavity phenomena cannot be neglected anymore. Here, we investigate this intermediate regime and show that the spectral and temporal properties of the photon pairs, as well as their emission rate, may significantly differ from the widely accepted linear model. The observed phenomena include frequency pulling and broadening in the temporal correlation for the down-converted optical fields. These factors need to be taken into account when devising practical applications of the high-rate cavity-assisted spontaneous PDC sources.
CRIS-Team WoS Importer:2020-08-21

Nonlinear Quantum Optics in a Millimeter Size Whispering Gallery Mode Resonator - Leuchs, Gerd; Marquardt, Christoph; Schwefel, Harald (Nonlinear Optics, NLO 2015, 2015)
Whispering gallery resonators made from nonlinear crystals offer high quality factors combined with small mode volumes leading to an enhanced effective X(2) nonlinearity. These properties facilitate studying quantum optical effects in the nonlinear regime with interacting fields differing in frequency by up to four orders of magnitude. Furthermore, the small size results in a large mode spacing allowing for heralded single photon generation in a single mode
CRIS-Team Scopus Importer:2022-06-05

Nonlinear single sideband microwave to optical conversion using an electro-optic WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2016)
Nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band is achieved within a crystalline whispering gallery mode resonator, reaching 0.1% photon number conversion efficiency with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Nonparaxial polarizers - Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Optics Letters, 2009)
We develop a theoretical description for polarizers that goes beyond the paraxial approximation. By combining existing theories for fields with nonplanar wavefronts, we are able to derive a simple power series expansion expressing the electric field of a light beam after a polarizer as a linear function of the field and its spatial derivatives evaluated before the polarizer. The first few terms of such expansion are explicitly given, and their physical meaning is discussed. © 2009 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Novel sources for polarisation squeezing and polarisation entanglement using photonic crystal fibres - Milanovic, Josip; Lassen, Mikael; Förtsch, Michael; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (CLEO/Europe - EQEC 2009 - European Conference on Lasers and Electro-Optics and the European Quantum Electronics Conference, 2009)
CRIS-Team Scopus Importer:2022-06-05

Observation of the Geometric Spin Hall Effect of Light - Korger, Jan; Aiello, Andrea; Chille, Vanessa; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2014)

Optical properties of a tilted polarizer and geometric spin hall effect of light - Korger, Jan; Aiello, Andrea; Gabriel, Christian; Banzer, Peter; Kolb, Tobias; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Optimally cloned binary coherent states - Müller, Christian; Leuchs, Gerd; Marquardt, Christoph; Andersen, U. L. (Physical Review A, 2017)
Binary coherent state alphabets can be represented in a two-dimensional Hilbert space. We capitalize this formal connection between the otherwise distinct domains of qubits and continuous variable states to map binary phase-shift keyed coherent states onto the Bloch sphere and to derive their quantum-optimal clones. We analyze the Wigner function and the cumulants of the clones, and we conclude that optimal cloning of binary coherent states requires a nonlinearity above second order. We propose several practical and near-optimal cloning schemes and compare their cloning fidelity to the optimal cloner.
CRIS-Team Scopus Importer:2022-06-05

Optimal working points for continuous-variable quantum channels - Khan, Imran; Wittmann, Christoffer; Jain, Nitin; Killoran, Nathan; Luetkenhaus, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2013)
The most important ability of a quantum channel is to preserve the quantum properties of transmitted quantum states. We experimentally demonstrate a continuous-variable system for efficient benchmarking of quantum channels. We probe the tested quantum channels for a wide range of experimental parameters such as amplitude, phase noise, and channel lengths up to 40 km. The data is analyzed using the framework of effective entanglement. We subsequently are able to deduce an optimal point of operation for each quantum channel with respect to the rate of distributed entanglement. This procedure is a promising candidate for benchmarking quantum nodes and individual links in large quantum networks of different physical implementations. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Optimizing the interaction of light with a single atom in free space - Srivathsan, Bharath; Fischer, Martin; Averchenko, V. A.; Alber, Lucas; Strekalov, D. V.; Marquardt, Christoph; Sondermann, Markus; Leuchs, Gerd (abstracts of the report at the conference, 2018)

Overcoming vacuum noise: The unforeseen benefits of quantum heterodyne detection - Müller, C. R.; Peuntinger, C.; Dirmeier, T.; Khan, I.; Vogl, U.; Marquardt, Christoph; Leuchs, Gerd; Sánchez-Soto, L. L.; Teo, Y. S.; Hradil, Z.; Rehácek, J. (Optics InfoBase Conference Papers, 2016)
Homodyne tomography and heterodyne detection are principal measurement schemes in continuous-variable quantum information and provide different accuracies in determining the quantum state of a system. The former allows for a tomographic reconstruction of the Wigner function of the state, whereas the latter directly samples its Husimi Q-function. We experimentally demonstrate that contrary to a common belief, heterodyne detection outperforms homodyne tomography for almost all Gaussian states.
CRIS-Team Scopus Importer:2022-06-05

Parsing polarization squeezing into Fock layers - Müller, Christian; Madsen, Lars S.; Klimov, Andrei B.; Sanchez-Soto, Luis L.; Leuchs, Gerd; Marquardt, Christoph; Andersen, Ulrik L. (Physical Review A, 2016)
We investigate polarization squeezing in squeezed coherent states with varying coherent amplitudes. In contrast to the traditional characterization based on the full Stokes parameters, we experimentally determine the Stokes vector of each excitation subspace separately. Only for states with a fixed photon number do the methods coincide; when the photon number is indefinite, we parse the state in Fock layers, finding that substantially higher squeezing can be observed in some of the single layers. By capitalizing on the properties of the Husimi Q function, we map this notion onto the Poincaré space, providing a full account of the measured squeezing.
CRIS-Team Scopus Importer:2022-06-05

Phase-locking an interferometer with single-photon detections - Hacker, Bastian; Günthner, Kevin; Rößler, Conrad; Marquardt, Christoph (New Journal of Physics, 2023)
We report on a novel phase-locking technique for fiber-based Mach-Zehnder interferometers based on discrete single-photon detections, and demonstrate this in a setup. Our interferometer decodes relative-phase-encoded optical pulse pairs for quantum key distribution applications and requires no locking laser in addition to the weak received signal. Our new simple locking scheme is shown to produce an Ornstein-Uhlenbeck dynamic and achieve optimal phase noise for a given count rate. In case of wavelength drifts that arise during the reception of Doppler-shifted satellite signals, the arm-length difference gets continuously readjusted to keep the interferometer phase stable.
CRIS-Team Scopus Importer:2023-12-01
Keywords: feedback; interferometry; Mach-Zehnder; phase-locking; quantum communication; quantum key distribution; single-photon detection

Phase noise suppression in Microstructured Fibers - Korn, Alexander; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Andersen, Ulrik Lund; Leuchs, Gerd (International Quantum Electronics Conference 2004, 2004)
We investigated thermal phase-noise in a microstructured fiber. We demonstrate that the microstructure of the fiber establishes a low order acoustic resonator thus suppressing all guided acoustic wave Brillouin scattering modes up to 300 MHz.<br

Polarization correlations in quantum optics - Sánchez-Soto, L. L.; Klimov, A. B.; Björk, G.; Söderholm, J.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
The standard degree of polarization involves exclusively first-order moments of the Stokes variables. This may be sufficient for most classical problems, but for quantum fields higher-order correlations are crucial. We claim that a complete polarization characterization must involve a whole hierarchy of polarization degrees constructed order by order, as it happens in coherence theory. We present here a second-order degree and determine it experimentally. ©2011 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Polarization-entangled photons from a whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Leuchs, Gerd; Marquardt, Christoph (npj Quantum Information, 2024)
Crystalline whispering gallery mode resonators (WGMRs) have been shown to facilitate versatile sources of quantum states that can efficiently interact with atomic systems. These features make WGMRs an efficient platform for quantum information processing. Here, we experimentally show that it is possible to generate polarization entanglement from WGMRs by using an interferometric scheme. Our scheme gives us the flexibility to control the phase of the generated entangled state by changing the relative phase of the interferometer. The S value of Clauser–Horne–Shimony–Holt’s inequality in the system is 2.45 ± 0.07, which violates the inequality by more than six standard deviations.<br
Keywords: Nonlinear optics; Quantum optics

Polarization entanglement from a crystalline whispering gallery resonator - Huang, Sheng-Hsuan; Dirmeier, Thomas; Shafiee, Golnoush; Laiho, Kaisa; Strekalov, Dmitry V.; Leuchs, Gerd; Marquardt, Christoph (CLEO 2024, 2024)
Polarization entanglement has not yet been shown in crystalline whispering gallery resonators. Here, we generate polarization entanglement by using an interferometric scheme. The S value of the Clauser-Horne-Shimony-Holt’s inequality in the system is 2.54 ± 0.06, in clear violation of the local realism.<br

Polarization noise induced by photon-phonon interaction in hollow-core photonic crystal fibres - Zhong, W.; Heim, B.; Elser, D.; Marquardt, Christoph; Leuchs, Gerd (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Guided acoustic wave Brillouin scattering (GAWBS), a weak forward scattering that stems from the interaction of light with thermally excited transverse phonons, has been studied in both standard fibres [1] and photonic crystal fibres [2, 3]. The acoustic phonon vibrations modulate the stress distribution in the silica fibre core, thus modulating the refractive index and inducing polarization and phase noise in the light field. © 2011 IEEE.
CRIS-Team Scopus Importer:2022-06-05

Polarization-Selective Out-Coupling of Whispering-Gallery Modes - Sedlmeir, Florian; Foreman, Matthew R.; Vogl, Ulrich; Zeltner, Richard; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Leuchs, Gerd; Schwefel, Harald G. L. (Physical Review Applied, 2017)
Whispering-gallery mode (WGM) resonators are an important platform for linear, nonlinear, and quantum optical experiments. In such experiments, independent control of in-coupling and out-coupling rates to different modes can lead to higher conversion efficiencies and greater flexibility in the generation of nonclassical states based on parametric down-conversion. In this work, we introduce a scheme that enables selective out-coupling of WGMs belonging to a specific polarization family, while the orthogonally polarized modes remain largely unperturbed. Our technique utilizes material birefringence in both the resonator and the coupler such that a negative (positive) birefringence allows for polarization-selective coupling to TE (TM) WGMs. We formulate a refined coupling condition suitable for describing the case where the refractive indices of the resonator and the coupler are almost the same, from which we derive a criterion for polarization-selective coupling. Finally, we experimentally demonstrate our proposed method using a lithium niobate disk resonator coupled to a lithium niobate prism, where we show a 22-dB suppression of coupling to TM modes relative to TE modes.
CRIS-Team Scopus Importer:2022-06-05

Polarization squeezing with photonic crystal fibers - Milanovic, Josip; Heersink, Joel; Marquardt, Christoph; Huck, A.; Andersen, Ulrik Lund; Leuchs, Gerd (Laser Physics, 2007)
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.polari

Practical continuous variable QKD in fiber and free space systems - Marquardt, Christoph (Frontiers in Optics 2016, 2016)
I will review recent activities in continuous variable QKD that aims for the deployment of QKD equipment compatible with current telecom standards and research in satellite QKD that will make it possible to bridge long distances.<br

Practical limits of an optimized quantum receiver - Marquardt, Christoph; Müller, Christian R.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2014)
We present a quantum receiver for the discrimination of quadrature phase-shift keyed signals that approaches the Helstrom bound for any signal power and discuss the influence of practical limitations. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Probabilistic amplification and cloning of phase-covariant coherent states - Müller, C. R.; Wittmann, C.; Marek, P.; Filip, R.; Usuga, M. A.; Marquardt, Christoph; Andersen, U. L.; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Probabilistic cloning of coherent states without a phase reference - Mueller, Christian R.; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Leuchs, Gerd; Andersen, Ulrik L. (Physical Review A - Atomic, Molecular, and Optical Physics, 2012)
We present a probabilistic cloning scheme operating independently of any phase reference. The scheme is based solely on a phase-randomized displacement and photon counting, omitting the need for nonclassical resources and nonlinear materials. In an experimental implementation, we employ the scheme to clone coherent states from a phase covariant alphabet and demonstrate that the cloner is capable of outperforming the hitherto best-performing deterministic scheme. An analysis of the covariances between the output states shows that uncorrelated clones can be approached asymptotically. This simultaneously demonstrates how the effect of loss on coherent states can be compensated via noiseless preamplification. © 2012 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Proof-of-principle test of coherent-state continuous variable quantum key distribution through turbulent atmosphere - Derkach, Ivan; Peuntinger, Christian; Ruppert, Laszlo; Heim, Bettina; Gunthner, Kevin; Usenko, Vladyslav C.; Elser, Dominique; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd (SPIE Security + Defence, 2016)
Continuous-variable quantum key distribution is a practical application of quantum information theory that is aimed at generation of secret cryptographic key between two remote trusted parties and that uses multi-photon quantum states as carriers of key bits. Remote parties share the secret key via a quantum channel, that presumably is under control of of an eavesdropper, and which properties must be taken into account in the security analysis. Well-studied fiber-optical quantum channels commonly possess stable transmittance and low noise levels, while free-space channels represent a simpler, less demanding and more flexible alternative, but suffer from atmospheric effects such as turbulence that in particular causes a non-uniform transmittance distribution referred to as fading. Nonetheless free-space channels, providing an unobstructed line-of-sight, are more apt for short, mid-range and potentially long-range (using satellites) communication and will play an important role in the future development and implementation of QKD networks. It was previously theoretically shown that coherent-state CV QKD should be in principle possible to implement over a free-space fading channel, but strong transmittance fluctuations result in the significant modulation-dependent channel excess noise. In this regime the post-selection of highly transmitting sub-channels may be needed, which can even restore the security of the protocol in the strongly turbulent channels. We now report the first proof-of-principle experimental test of coherent state CV QKD protocol using different levels Gaussian modulation over a mid-range (1.6-kilometer long) free-space atmospheric quantum channel. The transmittance of the link was characterized using intensity measurements for the reference but channel estimation using the modulated coherent states was also studied. We consider security against Gaussian collective attacks, that were shown to be optimal against CV QKD protocols . We assumed a general entangling cloner collective attack (modeled using data obtained from the state measurement results on both trusted sides of the protocol), that allows to purify the noise added in the quantum channel . Our security analysis of coherent-state protocol also took into account the effect of imperfect channel estimation, limited post-processing efficiency and finite data ensemble size on the performance of the protocol. In this regime we observe the positive key rate even without the need of applying post-selection. We show the positive improvement of the key rate with increase of the modulation variance, still remaining low enough to tolerate the transmittance fluctuations. The obtained results show that coherent-state CV QKD protocol that uses real free-space atmospheric channel can withstand negative influence of transmittance fluctuations, limited post-processing efficiency, imperfect channel estimation and other finite-size effects, and be successfully implemented. Our result paves the way to the full-scale implementation of the CV QKD in real free-space channels at mid-range distances.<br

QPSK receiver outperforming the standard quantum limit for any signal power - Muller, Christian R.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2014)
We present a quantum receiver for the discrimination of quadrature phase-shiftkeyed signals that approaches the Helstrom bound for any signal power. The discrimination isperformed via adaptive displacements prior to a single photon detector. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Quadrature phase shift keying coherent state discrimination via a hybrid receiver - Müller, Christian; Usuga, M. A.; Wittmann, Christoffer; Takeoka, M.; Marquardt, Christoph; Andersen, U. L.; Leuchs, Gerd (New Journal of Physics, 2012)
We propose and experimentally demonstrate a near-optimal discrimination scheme for the quadrature phase shift keying (QPSK) protocol. We show in theory that the performance of our hybrid scheme is superior to the standard scheme-heterodyne detection-for all signal amplitudes and underpin the predictions with our experimental results. Furthermore, our scheme provides hitherto the best performance in the domain of highly attenuated signals. The discrimination is composed of a quadrature measurement, a conditional displacement and a threshold detector. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

Quantum communication with coherent states of light - Khan, Imran; Elser, Dominique; Dirmeier, Thomas; Marquardt, Christoph; Leuchs, Gerd (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2017)
Quantum communication offers long-term security especially, but not only, relevant to government and industrial users. It is worth noting that, for the first time in the history of cryptographic encoding, we are currently in the situation that secure communication can be based on the fundamental laws of physics (information theoretical security) rather than on algorithmic security relying on the complexity of algorithms, which is periodically endangered as standard computer technology advances. On a fundamental level, the security of quantum key distribution (QKD) relies on the non-orthogonality of the quantum states used. So even coherent states are well suited for this task, the quantum states that largely describe the light generated by laser systems. Depending on whether one uses detectors resolving single or multiple photon states or detectors measuring the field quadratures, one speaks of, respectively, a discrete- or a continuous-variable description. Continuous-variable QKD with coherent states uses a technology that is very similar to the one employed in classical coherent communication systems, the backbone of today's Internet connections. Here, we review recent developments in this field in two connected regimes: (i) improving QKD equipment by implementing front-end telecom devices and (ii) research into satellite QKD for bridging long distances by building upon existing optical satellite links.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Coherent states; Continuous variables; Quantum communication

Quantum cryptography with twisted photons through an outdoor underwater channel - Bouchard, Frederic; Sit, Alicia; Hufnagel, Felix; Abbas, Aazad; Zhang, Yingwen; Heshami, Khabat; Fickler, Robert; Marquardt, Christoph; Leuchs, Gerd; Boyd, Robert W.; Karimi, Ebrahim (Optics Express, 2018)
Quantum communication has been successfully implemented in optical fibres and through free-space. Fibre systems, though capable of fast key and low error rates, are impractical in communicating with destinations without an established fibre link. Free-space quantum channels can overcome such limitations and reach long distances with the advent of satellite-to-ground links. However, turbulence, resulting from local fluctuations in refractive index, becomes a major challenge by adding errors and losses. Recently, an interest in investigating the possibility of underwater quantum channels has arisen. Here, we investigate the effect of turbulence on an underwater quantum channel using twisted photons in outdoor conditions. We study the effect of turbulence on transmitted error rates, and compare different quantum cryptographic protocols in an underwater quantum channel, showing the feasibility of high-dimensional encoding schemes. Our work may open the way for secure high-dimensional quantum communication between submersibles, and provides important input for potential submersibles-to-satellite quantum communication.
CRIS-Team Scopus Importer:2022-06-05

Quantum effects in optical fibers - Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2011)
The quantization of the light field is important for understanding some aspects of optical fiber systems: the quantum limit of amplifiers, the dynamics of solitons below shot noise and the appearance of non-classical light. © OSA/OFC/NFOEC 2011.
CRIS-Team Scopus Importer:2022-06-05

Quantum fiber solitons - generation, entanglement and detection - Leuchs, Gerd; Korolkova, Natalia; Glöckl, Oliver; Lorenz, Stefan; Heersink, Joel; Silberhorn, Christine; Marquardt, Christoph; Andersen, Ulrik L. (Quantum Information Processing: Schwerpunktprogramm 1078 der Deutschen Forschungsgemeinschaft, 2005)
UnivIS-Import:2015-04-20:Pub.2005.nat.dphy.optik.1optik.quantu_4
Keywords: Bright entangled beams; Entanglement of bright beams; Entanglement swapping; Non-separability; Polarization variables; Quantum correlations; Quantum fiber solitons; Quantum information processing; Sub-shot-noise phase quadrature measurements on intense beams

Quantum hacking of continuous-variable quantum key distribution systems: Realtime Trojan-horse attacks - Stiller, Birgit; Khan, Imran; Jain, Nitin; Jouguet, P.; Kunz-Jacques, S.; Diamanti, E.; Marquardt, Christoph; Leuchs, Gerd (Conference on Lasers and Electro-Optics Europe - Technical Digest, 2015)
We experimentally demonstrate successful Trojan-horse attacks on laboratory and commercial continuous-variable quantum key distribution systems with binary and Gaussian modulation. Furthermore, we analyze appropriate countermeasures regarding their spectral performance.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Optical pulses; Optical refraction; Optical variables control; Phase modulation; Protocols; Security

Quantum Light from a Whispering-Gallery-Mode Disk Resonator - Fuerst, J. U.; Strekalov, D. V.; Elser, Dominique; Aiello, Andrea; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2011)
Optical parametric down-conversion has proven to be a valuable source of nonclassical light. The process is inherently able to produce twin-beam correlations along with individual intensity squeezing of either parametric beam, when pumped far above threshold. Here, we present for the first time the direct observation of intensity squeezing of -1.2dB of each of the individual parametric beams in parametric down-conversion by use of a high quality whispering-gallery-mode disk resonator. In addition, we observed twin-beam quantum correlations of -2.7dB with this cavity. Such resonators feature strong optical confinement and offer tunable coupling to an external optical field. This work exemplifies the potential of crystalline whispering-gallery-mode resonators for the generation of quantum light. The simplicity of this device makes the application of quantum light in various fields highly feasible. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Quantum-like nonseparable structures in optical beams - Aiello, Andrea; Töppel, Falk; Marquardt, Christoph; Giacobino, Elisabeth; Leuchs, Gerd (New Journal of Physics, 2015)
When two or more degrees of freedom become coupled in a physical system, a number of observables of the latter cannot be represented by mathematical expressions separable with respect to the different degrees of freedom. In recent years it appeared clear that these expressions may display the same mathematical structures exhibited by multiparty entangled states in quantum mechanics. In this work, we investigate the occurrence of such structures in optical beams, a phenomenon that is often referred to as 'classical entanglement'. We present a unified theory for different kinds of light beams exhibiting classical entanglement and we indicate several possible extensions of the concept. Our results clarify and shed new light upon the physics underlying this intriguing aspect of classical optics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: classical entanglement; non-separability; optical beams

Quantum-limited measurements of intensity noise levels in Yb-doped fiber amplifiers - Popp, Alexandra; Distler, Victor; Jaksch, Kevin; Sedlmeir, Florian; Mueller, Christian R.; Haarlammert, Nicoletta; Schreiber, Thomas; Marquardt, Christoph; Tuennermann, Andreas; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2020)
We investigate the frequency-resolved intensity noise spectrum of an Yb-doped fiber amplifier down to the fundamental limit of quantum noise. We focus on the kHz and low MHz frequency regime with special interest in the region between 1 and 10 kHz. Intensity noise levels up to ≥ 60 dB above the shot noise limit are found, revealing great optimization potential. Additionally, two seed lasers with different noise characteristics were amplified, showing that the seed source has a significant impact and should be considered in the design of high power fiber amplifiers.
CRIS-Team Scopus Importer:2020-07-24

Quantum-limited measurements of optical signals from a geostationary satellite - Günthner, Kevin; Khan, Imran; Elser, Dominique Alexander; Stiller, Birgit; Bayraktar, Ömer; Mueller, Christian R.; Saucke, Karen; Troendle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optica, 2017)
The measurement of quantum signals that travel through long distances is fundamentally and technologically interesting. We present quantum-limited coherent measurements of optical signals that are sent from a satellite in geostationary Earth orbit to an optical ground station. We bound the excess noise that the quantum states could have acquired after having propagated 38,600 km through Earth’s gravitational potential, as well as its turbulent atmosphere. Our results indicate that quantum communication is feasible, in principle, in such a scenario, highlighting the possibility of a global quantum key distribution network for secure communication.
CRIS-Team Scopus Importer:2021-06-29
Keywords: (010.1300) Atmospheric propagation; (060.1660) Coherent communications; (060.2605) Free-space optical communication; (270.5565) Quantum communications; (270.5568) Quantum cryptography

Quantum-limited measurements of optical signals from a satellite in geostationary earth orbit - Günthner, Kevin; Khan, Imran; Elser, Dominique; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2021-06-29

Quantum-limited measurements of signals from geostationary earth orbit - Elser, Dominique; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (European Conference on Optical Communication, ECOC, 2016)
Quantum key distribution (QKD) has been implemented in metropolitan area networks around the world. Optical satellite communication is seen as suitable to provide the missing long-haul interconnections. We validate this approach by quantum measurements of optical signals from space.
CRIS-Team Scopus Importer:2021-06-29

Quantum Limits of Coherent Beam Combining - Leuchs, Gerd; Müller, Christian; Sedlmeir, Florian; Chatterjee, Sourav; Haarlammert, Nicoletta; Jauregui, Cesar; Schreiber, Thomas; Limpert, Jens; Tunnermann, Andreas; Marquardt, Christoph (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
Coherent beam combining refers to the process of generating a bright output beam by merging independent input beams with locked relative phases. We report the first quantum mechanical noise limit calculations for coherent beam combining and compare our results to quantum-limited amplification. We highlight a favourable noise scaling for both pure and noisy input states.
CRIS-Team Scopus Importer:2019-05-21

Quantum measurements of signals from the Alphasat TDP1 laser communication terminal - Elser, D.; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Bayraktar, Ömer; Müller, Christian; Saucke, K.; Tröndle, D.; Heine, F.; Seel, S.; Greulich, P.; Zech, H.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Quantum optics [1] can be harnessed to implement cryptographic protocols that are verifiably immune against any conceivable attack [2]. Even quantum computers, that will break most current public keys [3, 4], cannot harm quantum encryption. Based on these intriguing quantum features, metropolitan quantum networks have been implemented around the world [5-15]. However, the long-haul link between metropolitan networks is currently missing [16]. Existing fiber infrastructure is not suitable for this purpose since classical telecom repeaters cannot relay quantum states [2]. Therefore, optical satellite-to-ground communication [17-22] lends itself to bridge intercontinental distances for quantum communication [23-40].
CRIS-Team Scopus Importer:2021-06-29

Quantum nature of Gaussian discord: Experimental evidence and role of system-environment correlations - Chille, Vanessa; Quinn, Niall; Peuntinger, Christian; Croal, Callum; Mista, Ladislav; Marquardt, Christoph; Leuchs, Gerd; Korolkova, Natalia (Physical Review A - Atomic, Molecular, and Optical Physics, 2015)
We provide experimental evidence of quantum features in bipartite states classified as entirely classical according to a conventional criterion based on the Glauber P function but possessing nonzero Gaussian quantum discord. Their quantum nature is experimentally revealed by acting locally on one part of the discordant state. We experimentally verify and investigate the effect of discord increase under the action of local loss and link it to the entanglement with the environment. Adding an environmental system purifying the state, we unveil the flow of quantum correlations within a global pure system using the Koashi-Winter inequality. For a discordant state generated by splitting a state in which the initial squeezing is destroyed by random displacements, we demonstrate the recovery of entanglement highlighting the role of system-environment correlations.
CRIS-Team Scopus Importer:2022-06-05

Quantum physics in space - Belenchia, Alessio; Carlesso, Matteo; Bayraktar, Ömer; Dequal, Daniele; Derkach, Ivan; Gasbarri, Giulio; Herr, Waldemar; Li, Ying Lia; Rademacher, Markus; Sidhu, Jasminder; Oi, Daniel K.L.; Seidel, Stephan T.; et al. (Physics Reports-Review Section of Physics Letters, 2022)
Advances in quantum technologies are giving rise to a revolution in the way fundamental physics questions are explored at the empirical level. At the same time, they are the seeds for future disruptive technological applications of quantum physics. Remarkably, a space-based environment may open many new avenues for exploring and employing quantum physics and technologies. Recently, space missions employing quantum technologies for fundamental or applied studies have been proposed and implemented with stunning results. The combination of quantum physics and its space application is the focus of this review: we cover both the fundamental scientific questions that can be tackled with quantum technologies in space and the possible implementation of these technologies for a variety of academic and commercial purposes.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Quantum physics; Quantum technology; Space

Quantum polarization tomography of bright squeezed light - Mueller, C. R.; Stoklasa, B.; Peuntinger, Christian; Gabriel, C.; Rehacek, Jaroslav; Hradil, Zdenek; Klimov, A. B.; Leuchs, Gerd; Marquardt, Christoph; Sanchez-Soto, L. L. (New Journal of Physics, 2012)
We reconstruct the polarization sector of a bright polarization squeezed beam starting from a complete set of Stokes measurements. Given the symmetry that underlies the polarization structure of quantum fields, we use the unique SU(2) Wigner distribution to represent states. In the limit of localized bright states, the Wigner function can be approximated by an inverse threedimensional Radon transform. We compare this direct reconstruction with the results of a maximum likelihood estimation, thus finding excellent agreement. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

Quantum polarization tomography of bright squeezed light - Müller, C. R.; Stoklasa, B.; Peuntinger, C.; Gabriel, C.; Rehácek, J.; Hradil, Z.; Klimov, A. B.; Leuchs, Gerd; Marquardt, Christoph; Sánchez-Soto, L. L. (Frontiers in Optics, FIO 2012, 2012)
We reconstruct the polarization sector of a bright polarization squeezed beam starting from a complete set of Stokes measurements. We use both the inverse Radon transformation and a novel maximum likelihood algorithm. We find that the maximum likelihood reconstruction provides significantly higher statistical inversion stability, which allows us to get reconstructions of the same quality but from far smaller data sets. © OSA 2012.
CRIS-Team Scopus Importer:2022-06-05

Quantum random numbers based on the vacuum state - Gabriel, C.; Wittmann, C.; Sych, D.; Dong, R.; Mauerer, W.; Andersen, U. L.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2011)
CRIS-Team Scopus Importer:2022-06-05

Quantum reconstruction of an intense polarization squeezed optical state - Marquardt, Christoph; Heersink, Joel; Dong, Ruifang; Chekova, Maria; Klimov, Andrei B.; Sanchez-Soto, L. L.; Andersen, Ulrik L.; Leuchs, Gerd (Physical Review Letters, 2007)
We perform a reconstruction of the polarization sector of the density matrix of an intense polarization squeezed beam starting from a complete set of Stokes measurements. By using an appropriate quasidistribution, we map this onto the Poincaré space, providing a full quantum mechanical characterization of the measured polarization stat
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.quantu_3

Quantum State Reconstruction of an Intense Polarization Squeezed State - Marquardt, Christoph; Heersink, Joel; Chekhova, Maria V.; Klimov, A. B.; Sánchez-Soto, Luis L.; Andersen, Ulrik Lund; Leuchs, Gerd (Quantum Electronics and Laser Science Conference 2006, 2006)
The first quantum reconstruction of an intense Kerr squeezed state is reported. Taking into account the algebraic properties of the Stokes operators, the Wigner function describing a polarization squeezed state can also be fully reconstructed.<br

Quantum technologies in space - Kaltenbaek, Rainer; Acin, Antonio; Bacsardi, Laszlo; Bianco, Paolo; Bouyer, Philippe; Diamanti, Eleni; Marquardt, Christoph; Omar, Yasser; Pruneri, Valerio; Rasel, Ernst Maria; Sang, Bernhard; Seidel, Stephan T.; et al. (Experimental Astronomy, 2021)
Recently, the European Commission supported by many European countries has announced large investments towards the commercialization of quantum technology (QT) to address and mitigate some of the biggest challenges facing today's digital era - e.g. secure communication and computing power. For more than two decades the QT community has been working on the development of QTs, which promise landmark breakthroughs leading to commercialization in various areas. The ambitious goals of the QT community and expectations of EU authorities cannot be met solely by individual initiatives of single countries, and therefore, require a combined European effort of large and unprecedented dimensions comparable only to the Galileo or Copernicus programs. Strong international competition calls for a coordinated European effort towards the development of QT in and for space, including research and development of technology in the areas of communication and sensing. Here, we aim at summarizing the state of the art in the development of quantum technologies which have an impact in the field of space applications. Our goal is to outline a complete framework for the design, development, implementation, and exploitation of quantum technology in space.<br
Keywords: Quantum technology; Entanglement; Fundamental tests; Quantum communication; Quantum sensing

Quantum uncertainty in the beam width for optical spatial modes - Chille, Vanessa; Aiello, Andrea; Banzer, Peter; Leuchs, Gerd; Marquardt, Christoph; Treps, Nicolas; Fabre, Claude (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We theoretically investigate the quantum uncertainty in the width of optical beams. Many optical applications such as imaging and beam focusing are limited by the quantum noise in spatial characteristics of light beams.
CRIS-Team Scopus Importer:2022-06-05

Quantum uncertainty in the beam width of spatial optical modes - Chille, Vanessa; Banzer, Peter; Aiello, Andrea; Leuchs, Gerd; Marquardt, Christoph; Treps, Nicolas; Fabre, Claude (Optics Express, 2015)
We theoretically investigate the quantum uncertainty in the beam width of transverse optical modes and, for this purpose, define a corresponding quantum operator. Single mode states are studied as well as multimode states with small quantum noise. General relations are derived, and specific examples of different modes and quantum states are examined. For the multimode case, we show that the quantum uncertainty in the beam width can be completely attributed to the amplitude quadrature uncertainty of one specific mode, which is uniquely determined by the field under investigation. This discovery provides us with a strategy for the reduction of the beam width noise by an appropriate choice of the quantum state.
CRIS-Team Scopus Importer:2022-06-05

QUBE-II - Quantum Key Distribution with a CubeSat - Hutterer, Martin; Auer, Michael; Baliuka, Adomas; Bayraktar, Ömer; Freiwang, Peter; Gall, Marcell; Günthner, Kevin; Haber, Roland; Janusch, Janko; Knips, Lukas; Kobel, Pascal; Krauss, Markus; et al. (IAC-22-B4.9-GTS.5.5,x70823, 2022)
Keywords: QKD; CubeSat; QUBE; Quantum Payload; Quantum Mechanics; QRNG

Qube - Quantum key distribution with CubeSat - Lemke, Norbert M.K.; Weinfurter, Harald; Marquardt, Christoph; Moll, Florian; Haber, Roland; Grünefeld, Matthias; Seidel, Stephan T.; Freiwang, Peter; Rosenfeld, Wenjamin; Bayraktar, Ömer; Rödiger, Benjamin; Schmidt, Christopher; et al. (Proceedings of the International Astronautical Congress, IAC, 2018)
QUBE (Quantum Key Distribution with CubeSat) is one out of three pilot projects in the frame of the national German initiative QUTEGA to promote quantum technologies. The project is funded by the German Federal Ministry of Education and Research (BMBF) with co-funding of industry as preparation for the European flagship on Quantum Technology. With the current development pace in quantum computation, it has been predicted that in less than two decades quantum computers will be able to break encryption codes deployed today, which are currently based on mathematical problems difficult to solve with classical computation. This shows the urgent need for quantum-safe encryption that is resistant to attacks of both, quantum and classical, computers. A long term solution for quantum-safe encryption is the use of a completely random, so-called One-Time-Pad generated with true Random Number Generation (RNG) and distributed via Quantum Key Distribution (QKD). The QKD in fiber networks is limited to approx. 100 km due to damping within the carrier medium. For longer distances so far only satellite based techniques are able to transmit the keys. As a pathfinder, QUBE plans perform an in-orbit demonstration of the core technologies on a CubeSat platform.
CRIS-Team Scopus Importer:2022-06-05
Keywords: CubeSat; QKD; QRNG; Quantum Mechanics; QUBE

QUBE – Towards Quantum Key Distribution with Small Satellites - Knips, Lukas; Auer, Michael; Baliuka, Adomas; Bayraktar, Ömer; Freiwang, Peter; Grünefeld, Matthias; Haber, Roland; Lemke, Norbert; Marquardt, Christoph; Moll, Florian; Pudelko, Jonas; Rödiger, Benjamin; et al. (Optics InfoBase Conference Papers, 2022)
Quantum Key Distribution (QKD) in space will be integral for future quan-tum networks. The space mission QUBE will test novel integrated optics components in a three-unit CubeSat demonstrating an economic route for global-scale QKD.
CRIS-Team Scopus Importer:2022-09-02

R&D advances for quantum communication systems - Leuchs, Gerd; Marquardt, Christoph; Sánchez-Soto, Luis L.; Strekalov, Dmitry V. (Elsevier, 2019)
Understanding the nature of light leads to the question of how the principles of quantum physics can be harnessed in practical optical communication. A deeper understanding of fundamental physics has always advanced technology. However, the quantum principles certainly have a distinctly limiting character when looked upon from the engineering point of view. A particle cannot have well-defined momentum and position at the same time. An informative measurement will unpredictably alter the state of a quantum object. One cannot reliably clone an arbitrary quantum state. These and a number of other similar principles give rise to what is commonly known as the quantum “no-go theorems”-a disconcerting term when it comes to building something practical. And yet a search for novel principles of communication enabled by quantum physics began already in its early days and has only intensified since. On this path physicists are faced with a remarkable challenge: to turn a series of negative statements into new technological recipes.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Additive white gaussian noise; Local oscillator; Quantum communication systems; Quantum key distribution; Shannon entropy; Signal-to-noise ratio

Recent Developments in Quantum Key Distribution - Marquardt, Christoph (Optical Fiber Communication Conference (OFC) 2024, 2024)
I will introduce the principles and requirements of quantum key distribution in realistic scenarios and applications. Furthermore I will highlight advances and developments in the field in the technical and architectural domain.<br

Reduction of guided acoustic wave brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Andersen, Ulrik Lund; Korn, Alexander; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2006)
Guided acoustic wave Brillouin scattering (GAWBS) generates phase and polarization noise of light propagating in glass fibers. This excess noise affects the performance of various experiments operating at the quantum noise limit. We experimentally demonstrate the reduction of GAWBS noise in a photonic crystal fiber in a broad frequency range by tailoring the acoustic modes using the photonic also as a phononic crystal. We compare the noise spectrum to the one of a standard fiber and observe a tenfold noise reduction in the frequency range up to 200 MHz. Based on our measurement results as well as on numerical simulations, we establish a model for the reduction of GAWBS noise in photonic crystal fibers. © 2006 The American Physical Society.
Created from Fastlane, Scopus look-up

Risk analysis of Trojan-horse attacks on practical quantum key distribution systems - Jain, Nitin; Stiller, Birgit; Khan, Imran; Makarov, Vadim; Marquardt, Christoph; Leuchs, Gerd (IEEE Journal of Selected Topics in Quantum Electronics, 2015)
An eavesdropper Eve may probe a quantum key distribution (QKD) system by sending a bright pulse from the quantum channel into the system and analyzing the back-reflected pulses. Such Trojan-horse attacks can breach the security of the QKD system, if appropriate safeguards are not installed or if they can be fooled by the Eve. We present a risk analysis of such attacks based on extensive spectral measurements, such as transmittance, reflectivity, and detection sensitivity of some critical components used in a typical QKD systems. Our results indicate the existence of wavelength regimes, where the attacker gains considerable advantage as compared to launching an attack at 1550 nm. We also propose countermeasures to reduce the risk of such attacks.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Electrooptic modulators; Fiber optics; Infrared detectors; Infrared spectra; Optical pulses; Optical receivers; Photodetectors; Quantum cryptography; Quantum key distribution; Reflectometry; Supercontinuum; Transmittance; Trojan-horse attack

Satellite-based QKD - Khan, Imran; Heim, Bettina; Neuzner, Andreas; Marquardt, Christoph (Optics and Photonics News, 2018)
CRIS-Team Scopus Importer:2022-06-05

Satellite quantum communication via the alphasat laser communication terminal quantum signals from 36 thousand kilometers above earth - Elser, Dominique Alexander; Günthner, Kevin; Khan, Imran; Stiller, Birgit; Marquardt, Christoph; Leuchs, Gerd; Saucke, Karen; Tröndle, Daniel; Heine, Frank; Seel, Stefan; Greulich, Peter; Zech, Herwig; et al. (2015 IEEE International Conference on Space Optical Systems and Applications, ICSOS 2015, 2016)
By harnessing quantum effects, we nowadays can use encryption that is in principle proven to withstand any conceivable attack. These fascinating quantum features have been implemented in metropolitan quantum networks around the world. In order to interconnect such networks over long distances, optical satellite communication is the method of choice. Standard telecommunication components allow one to efficiently implement quantum communication by measuring field quadratures (continuous variables). This opens the possibility to adapt our Laser Communication Terminals (LCTs) to quantum key distribution (QKD). First satellite measurement campaigns are currently validating our approach.
CRIS-Team Scopus Importer:2021-06-29
Keywords: free-space optical communication; quantum cryptography; quantum key distribution; satellite quantum communication; satellite-ground laser communication

Single-mode squeezing in arbitrary spatial modes - Semmler, Marion; Berg-Johansen, Stefan; Chille, Vanessa; Gabriel, Christian; Banzer, Peter; Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2016)
As the generation of squeezed states of light has become a standard technique in laboratories, attention is increasingly directed towards adapting the optical parameters of squeezed beams to the specific requirements of individual applications. It is known that imaging, metrology, and quantum information may benefit from using squeezed light with a tailored transverse spatial mode. However, experiments have so far been limited to generating only a few squeezed spatial modes within a given setup. Here, we present the generation of single-mode squeezing in Laguerre-Gauss and Bessel-Gauss modes, as well as an arbitrary intensity pattern, all from a single setup using a spatial light modulator (SLM). The degree of squeezing obtained is limited mainly by the initial squeezing and diffractive losses introduced by the SLM, while no excess noise from the SLM is detectable at the measured sideband. The experiment illustrates the single-mode concept in quantum optics and demonstrates the viability of current SLMs as flexible tools for the spatial reshaping of squeezed light.
CRIS-Team Scopus Importer:2022-06-05

Single sideband microwave to optical photon conversion-an electro-optic realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2017)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator.
CRIS-Team Scopus Importer:2021-06-29

Space QUEST mission proposal: Experimentally testing decoherence due to gravity - Joshi, Siddarth Koduru; Pienaar, Jacques; Ralph, Timothy C.; Cacciapuoti, Luigi; Mccutcheon, Will; Rarity, John; Giggenbach, Dirk; Lim, Jin Gyu; Makarov, Vadim; Fuentes, Ivette; Scheidl, Thomas; Beckert, Erik; et al. (New Journal of Physics, 2018)
Models of quantum systems on curved space-times lack sufficient experimental verification. Some speculative theories suggest that quantum correlations, such as entanglement, may exhibit different behavior to purely classical correlations in curved space. By measuring this effect or lack thereof, we can test the hypotheses behind several such models. For instance, as predicted by Ralph et al [5] and Ralph and Pienaar [1], a bipartite entangled system could decohere if each particle traversed through a different gravitational field gradient. We propose to study this effect in a ground to space uplink scenario. We extend the above theoretical predictions of Ralph and coworkers and discuss the scientific consequences of detecting/failing to detect the predicted gravitational decoherence. We present a detailed mission design of the European Space Agency's Space QUEST (Space - Quantum Entanglement Space Test) mission, and study the feasibility of the mission scheme.
CRIS-Team Scopus Importer:2022-06-05
Keywords: entanglement; gravitational decoherence; quantum communication; quantum mechanics; relativity; satellite

Squeezed light and self-induced transparency in mercury-filled hollow core photonic crystal fibers - Vogl, Ulrich; Joly, Nicolas Y.; Russell, Philip St. J.; Marquardt, Christoph; Leuchs, Gerd (Proceedings 2015 European Conference on Lasers and Electro-Optics - European Quantum Electronics Conference, CLEO/Europe-EQEC 2015, 2015)
We successfully demonstrate squeezing of nanosecond pulses via self-induced transparency in a system of mercury vapor confined in a hollow core kagomé-style fiber.
CRIS-Team Scopus Importer:2022-06-05

Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Shafiee, Golnoush; Dirmeier, Thomas; Vogl, Ulrich; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald G.L.; Gehring, Tobias; Andersen, Ulrik L.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2018)
We demonstrate the generation of squeezed vacuum states of light in a crystalline whispering gallery mode resonator. We utilize a millimeter-sized lithium niobate resonator with strong optical second order nonlinearity. This system allows us to reach 1.2 dB of squeezing at a pump power of only 300 μW and offers hereby a compact and power efficient source of squeezed vacuum states of light.
CRIS-Team Scopus Importer:2022-06-05

Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Vogl, Ulrich; Dirmeier, Thomas; Shafiee, Golnoush; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald; Gehring, Tobias; Andersen, Ulrik Lund; Leuchs, Gerd; Marquardt, Christoph (Optica, 2019)
Squeezed vacuum states enable optical measurements below the quantum limit and hence are a valuable resource for applications in quantum metrology and also quantum communication. However, most available sources require high pump powers in the milliwatt range and large setups that hinder real-world applications. Furthermore, degenerate operation of such systems presents a challenge. Here, we use a compact crystalline whispering gallery mode resonator made of lithium niobate as a degenerate parametric oscillator. We demonstrate about 1.4 dB noise reduction below the shot-noise level for only 300 mu W of pump power in degenerate single-mode operation. Furthermore, we report a record pump threshold as low as 1.35 mu W. Our results show that the whispering gallery-based approach presents a promising platform for a compact and efficient source for nonclassical light. (c) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-12-06

Squeezing by self induced transparency in Rb filled hollow core fibers - Zhong, Wenjia; Marquardt, Christoph; Leuchs, Gerd; Andersen, U. L.; Light, P; Couny, F.; Benabid, F. (2007 European Conference on Lasers and Electro-Optics and the International Quantum Electronics Conference, 2007)
There is great interest in photonic crystal fibers (PCFs) because of their potential for hosting highly nonlinear material. Already with material of low nonlinearity such as silica for solid core PCFs, the nonlinear properties can be utilized since high intensities of light are guided within the core. To create squeezed states, we plan to exploit the high nonlinearity of resonant Rb vapor filled in the hollow fiber core and to use self-induced transparency (SIT) solitons to avoid resonant loss. High nonlinearity is induced from the self-phase modulation of a detuned 2pi soliton. Photon-phonon interactions, which cause a significant amount of excess noise in solid core fibers, will be highly reduced in our system.<br
Keywords: Resonance; Optical fiber theory; Photonics; Crystalline materials; Fiber nonlinear optics; Optical solitons; Solids; Atom optics; Physics; Optical materials

Stabilization of transmittance fluctuations caused by beam wandering in continuous-variable quantum communication over free-space atmospheric channels - Usenko, Vladyslav C.; Peuntinger, Christian; Heim, Bettina; Guenthner, Kevin; Derkach, Ivan; Elser, Dominique; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd (Optics Express, 2018)
Transmittance fluctuations in turbulent atmospheric channels result in quadrature excess noise which limits applicability of continuous-variable quantum communication. Such fluctuations are commonly caused by beam wandering around the receiving aperture. We study the possibility to stabilize the fluctuations by expanding the beam, and test this channel stabilization in regard of continuous-variable entanglement sharing and quantum key distribution. We perform transmittance measurements of a real free-space atmospheric channel for different beam widths and show that the beam expansion reduces the fluctuations of the channel transmittance by the cost of an increased overall loss. We also theoretically study the possibility to share an entangled state or to establish secure quantum key distribution over the turbulent atmospheric channels with varying beam widths. We show the positive effect of channel stabilization by beam expansion on continuous-variable quantum communication as well as the necessity to optimize the method in order to maximize the secret key rate or the amount of shared entanglement. Being autonomous and not requiring adaptive control of the source and detectors based on characterization of beam wandering, the method of beam expansion can be also combined with other methods aiming at stabilizing the fluctuating free-space atmospheric channels.
CRIS-Team Scopus Importer:2022-06-05

Stratospheric QKD: Feasibility analysis and free-space optics system concept - Moll, Florian; Botter, Thierry; Marquardt, Christoph; Pusey, David; Shrestha, Amita; Reeves, Andrew; Jaksch, Kevin; Guenthner, Kevin; Bayraktar, Oemer; Mueller-Hirschkorn, Christian; Gallardo, Alberto Diago; Gonzalez, Dionisio Diaz; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Quantum key distribution (QKD) is one of the most mature quantum technologies and can provide quantum-safe security in future communication networks. Since QKD in fiber is limited to a range of few hundred kilometers, one approach to bridge continental scale distances may be the use of high altitude pseudo satellites (HAPS) as mobile trusted nodes in the stratosphere. In parallel, free-space laser communication for high rate data transmission has been a subject of research and development for several decades and its commercialization is progressing rapidly. Important synergies exist between classical free-space communication and QKD systems since the quantum states are often implemented using the same degrees of freedom such as polarization or field amplitude and phase. These synergies can be used to benefit from the progress in classical free-space laser communication in QKD applications. In this paper, the use case of QKD in a stratospheric environment is described wherein HAPS may serve as relay station of secret keys and encrypted data. The mission scenario and HAPS capabilities are analyzed to derive special requirements on the stratospheric laser terminal, the link geometry and the ground segment with respect to a feasibility demonstration. To obtain a flexible and compatible system, discrete variable and continuous variable QKD protocols are considered to be implemented side by side in the HAPS payload. Depending on the system parameters, it can be beneficial to use the one or the other kind of protocol. Thus, a direct comparison of both in one and the same system is of scientific interest. Each of the protocols has particular requirements on coupling efficiency and implementation. Link budget calculations are performed to analyze possible distances, key rates and data transmission rates for the different schemes. In case of the QKD system, the mean coupling efficiency is of main interest, i.e. signal fluctuations arising from atmospheric turbulence must be taken into account in the security proof, but the buffered key generation relaxes real-time requirements. This is different to classical communications, where the corresponding fading loss must be assessed. A system architecture is presented that comprises the optical aircraft terminal, the optical ground terminal and the most important subsystems that enable implementation of the considered QKD protocols. The aircraft terminal is interfaced with the dedicated quantum transmitter module (Alice) and the ground station with the dedicated quantum receiver module (Bob). The optical interfaces are SMF couplings which put high requirements on the receiving optics, in particular the need for wave-front correction with adaptive optics. The findings of the system study are reviewed and necessary next steps pointed out.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Communications system design; Free-Space Optical Communications; Quantum Key Distribution; Stratospheric communications

Strong optoacoustic interaction in hot CS2-filled liquid-core optical fiber - Geilen, Andreas; Popp, Alexandra; Walter, Daniel; Chemnitz, Mario; Junaid, Saher; Poulton, Christopher G.; Marquardt, Christoph; Schmidt, Markus A.; Stiller, Birgit (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Optical fibers with a liquid core provide a versatile platform for nonlinear optics [1]. Filled with carbon disulfide (CS 2 ), the high linear refractive index of 1.59 at 1549 nm and low speed of sound of 1250 ms -1 , compared to silica, ensures guidance of optical and acoustic waves inside the fiber core. This type of fiber also provides a large optoacoustic interaction via stimulated Brillouin scattering (SBS) [2] due to the high optical nonlinearity of CS 2 , as well as the long interaction length and the low optical loss.
CRIS-Team Scopus Importer:2021-10-29

Study of turbulence induced orbital angular momentum channel crosstalk in a 1.6km free-space optical link - Lavery, Martin P.J.; Heim, Bettina; Peuntinger, Christian; Magaña-Loaiza, Omar S.; Karimi, Ebrahim; Bauer, Thomas; Banzer, Peter; Marquardt, Christoph; Willner, Alan E.; Boyd, Robert W.; Padgett, Miles J.; Leuchs, Gerd (CLEO: Science and Innovations, CLEO-SI 2015, 2015)
We experimentally study the turbulence induced crosstalk between orbital angular momentum channels transmitted over a 1.6 km optical link. Our presented results indicate that turbulence mitigation techniques will be required for links of this length. © OSA 2015.
CRIS-Team Scopus Importer:2022-06-05

Superlinear threshold detectors in quantum cryptography - Lydersen, Lars; Jain, Nitin; Wittmann, Christoffer; Maroy, Oystein; Skaar, Johannes; Marquardt, Christoph; Makarov, Vadim; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2011)
We introduce the concept of a superlinear threshold detector, a detector that has a higher probability to detect multiple photons if it receives them simultaneously rather than at separate times. Highly superlinear threshold detectors in quantum key distribution systems allow eavesdropping the full secret key without being revealed. Here, we generalize the detector control attack, and analyze how it performs against quantum key distribution systems with moderately superlinear detectors. We quantify the superlinearity in superconducting single-photon detectors based on earlier published data, and gated avalanche photodiode detectors based on our own measurements. The analysis shows that quantum key distribution systems using detector(s) of either type can be vulnerable to eavesdropping. The avalanche photodiode detector becomes superlinear toward the end of the gate. For systems expecting substantial loss, or for systems not monitoring loss, this would allow eavesdropping using trigger pulses containing less than 120 photons per pulse. Such an attack would be virtually impossible to catch with an optical power meter at the receiver entrance. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Tackling Africa's digital divide 706 639/624/1075/187 comment - Lavery, Martin P. J.; Abadi, Mojtaba Mansour; Bauer, Ralf; Brambilla, Gilberto; Cheng, Ling; Cox, Mitchell A.; Dudley, Angela; Ellis, Andrew D.; Fontaine, Nicolas K.; Kelly, Anthony E.; Marquardt, Christoph; Matlhane, Selaelo; et al. (Nature Photonics, 2018)
CRIS-Team Scopus Importer:2022-06-05

Telecom Compatible Quantum Key Distribution - Learning from Classical Coherent Communication - Marquardt, Christoph (2019 Optical Fiber Communications Conference and Exhibition, OFC 2019 - Proceedings, 2019)
Quantum key distribution (QKD) enables secure cryptography that is safe against future attacks by quantum computers. We show recent advances in continuous variable QKD and highlight similarities and differences to classical coherent communication.
CRIS-Team Scopus Importer:2019-05-21

Temporal shaping of heralded photons in a resonator-assisted parametric down-conversion with modulated pump pulses - Averchenko, V. A.; Förtsch, M.; Fischer, M.; Aiello, A.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2022-06-05

Temporal shaping of single photons enabled by entanglement - Averchenko, Valentin; Sych, Denis; Schunk, Gerhard; Vogl, Ulrich; Marquardt, Christoph; Leuchs, Gerd (Physical Review A, 2017)
We present a method to produce pure single photons with an arbitrary designed temporal shape in a heralded way. As an indispensable resource, the method uses pairs of time-energy entangled photons. One photon of a pair undergoes temporal amplitude-phase modulation according to the desired shape. Subsequent frequency-resolved detection of the modulated photon heralds its entangled counterpart in a pure quantum state. The temporal shape of the heralded photon is indirectly affected by the modulation in the heralding arm. We derive conditions for which the shape of the heralded photon is given by the modulation function. The method can be implemented with various sources of time-energy entangled photons. In particular, using entangled photons from parametric down-conversion the method provides a simple means to generate pure shaped photons with an unprecedented broad range of temporal durations, from tenths of femtoseconds to microseconds. This shaping of single photons will push forward the implementation of scalable multidimensional quantum information protocols, efficient photon-matter coupling, and quantum control at the level of single quanta.
CRIS-Team Scopus Importer:2022-06-05

The deep space quantum link: prospective fundamental physics experiments using long-baseline quantum optics - Mohageg, Makan; Mazzarella, Luca; Anastopoulos, Charis; Gallicchio, Jason; Hu, Bei-Lok; Jennewein, Thomas; Johnson, Spencer; Lin, Shih-Yuin; Ling, Alexander; Marquardt, Christoph; Meister, Matthias; Newell, Raymond; et al. (EPJ Quantum Technology, 2022)
The National Aeronautics and Space Administration’s Deep Space Quantum Link mission concept enables a unique set of science experiments by establishing robust quantum optical links across extremely long baselines. Potential mission configurations include establishing a quantum link between the Lunar Gateway moon-orbiting space station and nodes on or near the Earth. This publication summarizes the principal experimental goals of the Deep Space Quantum Link. These goals, identified through a multi-year design study conducted by the authors, include long-range teleportation, tests of gravitational coupling to quantum states, and advanced tests of quantum nonlocality.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Foundational quantum mechanics; General relativity; Quantum optics

The photonic wheel - demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2013)

The polarization properties of a tilted polarizer - Korger, Jan; Kolb, Tobias; Banzer, Peter; Aiello, Andrea; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2013)
Polarizers are key components in optical science and technology. Thus, understanding the action of a polarizer beyond oversimplifying approximations is crucial. In this work, we study the interaction of a polarizing interface with an obliquely incident wave experimentally. To this end, a set of Mueller matrices is acquired employing a novel procedure robust against experimental imperfections. We connect our observation to a geometric model, useful to predict the effect of polarizers on complex light fields. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Thermodynamic Control of Nanoliter Volumes of CS2 via Stimulated Brillouin Scattering - Geilen, Andreas; Popp, Alexandra; Das, Debayan; Junaid, Saher; Poulton, Christopher; Chemnitz, Mario; Marquardt, Christoph; Schmidt, M. A.; Stiller, Birgit (Optics InfoBase Conference Papers, 2022)
We present Brillouin-Mandelstam measurements of hard-to-reach, thermodynamic regimes in fully-sealed, CS2-filled liquid-core optical fibers. We investigate the Brillouin response in the positive and negative pressure regimes for isochoric and isobaric processes.
CRIS-Team Scopus Importer:2023-04-20

The standard quantum limit of coherent beam combining - Müller, Christian; Sedlmeir, F.; Martynov, V. O.; Marquardt, Christoph; Andrianov, A. V.; Leuchs, Gerd (New Journal of Physics, 2019)
Coherent beam combining refers to the process of generating a bright output beam by merging independent input beams of individually diffusing relative phases by locking them to each other. We report the first quantum mechanical noise limit calculations for coherent beam combining and compare our results to quantum-limited amplification. Our coherent beam combining scheme is based on an optical Fourier transformation which renders the scheme compatible with integrated optics combined with feed-back stabilization of the relative phases. The scheme can belayed out for an arbitrary number of input beams and approaches the shot noise limit for a large number of inputs.
CRIS-Team WoS Importer:2019-10-15

Time-frequency multiplexed single-photon source based on LiNbO3 modulators - Massaro, Marcello; Ansari, Vahid; Schlue, Fabian; Luo, Kai Hong; Herrmann, Harald; Brecht, Benjamin; Silberhorn, Christine; Dirmeier, Thomas; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2020)
We present advances in the use of gigahertz LiNbO3 modulators enabling us programmable delays, which we will use to implement a multiplexed single-photon source, based on birefringent phase-matching in KTP waveguides.
CRIS-Team Scopus Importer:2020-11-13

Tools for detecting entanglement between different degrees of freedom in quadrature squeezed cylindrically polarized modes - Gabriel, C.; Aiello, Andrea; Berg-Johansen, S.; Marquardt, Christoph; Leuchs, Gerd (European Physical Journal D, 2012)
Quadrature squeezed cylindrically polarized modes contain entanglement not only in the polarization and spatial electric field variables but also between these two degrees of freedom [C. Gabriel et al., Phys. Rev. Lett. 106, 060502 (2011)]. In this paper we present tools to generate and detect this entanglement. Experimentally we demonstrate the generation of quadrature squeezing in cylindrically polarized modes by mode transforming a squeezed Gaussian mode. Specifically, -1.2dB ± 0.1 dB of amplitude squeezing are achieved in the radially and azimuthally polarized mode. Furthermore, theoretically it is shown how the entanglement contained within these modes can be measured and how strong the quantum correlations are, depending on the measurement scheme. © EDP Sciences, Società Italiana di Fisica, Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-06-05

Towards Integrating True Random Number Generation in Coherent Optical Transceivers - Milovancev, Dinka; Vokic, Nemanja; Pacher, Christoph; Khan, Imran; Marquardt, Christoph; Boxleitner, Winfried; Hubel, Hannes; Schrenk, Bernhard (IEEE Journal of Selected Topics in Quantum Electronics, 2020)
The integration of quantum communication functions often requires dedicated opto-electronic components that do not bode well with the technology roadmaps of telecom systems. We investigate the capability of commercial coherent transceiver sub-systems to support quantum random number generation next to classical data transmission, and demonstrate how the quantum entropy source based on vacuum fluctuations can be potentially converted into a true random number generator for this purpose. We discuss two possible implementations, building on a receiver- and a transmitter-centric architecture. In the first scheme, balanced homodyne broadband detection in a coherent intradyne receiver is exploited to measure the vacuum state at the input of a 90-degree hybrid. In our proof-of-principle demonstration, a clearance of >2 dB between optical and electrical noise is obtained over a wide bandwidth of more than 11 GHz. In the second scheme, we propose and evaluate the re-use of monitoring photodiodes of a polarization-multiplexed inphase/quadrature modulator for the same purpose. Time-interleaved random number generation is demonstrated for 10 Gbaud polarization-multiplexed quadrature phase shift keyed data transmission. The availability of detailed models will allow to calculate the extractable entropy and we accordingly show randomness extraction for our two proof-of-principle experiments, employing a two-universal strong extractor.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Digital security; Multi-purpose photonics; Optical communication equipment; Optical signal detection; Random number generation

Towards two-photon interference with a whispering gallery photon pair source - Schunk, Gerhard; Shafiee, Golnoush; Vogl, Ulrich; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schwefel, Harald G.L.; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2016)
Down-converted photons from counterpropagating whispering gallery modes can be used to generate two-photon interference. We present our experimental scheme and discuss the interference visibility in case of backscattering.
CRIS-Team Scopus Importer:2022-06-05

Transverse Angular Momentum and Geometric Spin Hall Effect of Light - Aiello, Andrea; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2009)
We present a novel fundamental phenomenon occurring when a polarized beam of light is observed from a reference frame tilted with respect to the direction of propagation of the beam. This effect has a purely geometric nature and amounts to a polarization-dependent shift or split of the beam intensity distribution evaluated as the time-averaged flux of the Poynting vector across the plane of observation. We demonstrate that such a shift is unavoidable whenever the beam possesses a nonzero transverse angular momentum. This latter result has general validity and applies to arbitrary systems such as, e.g., electronic and atomic beams. © 2009 The American Physical Societ
UnivIS-Import:2015-03-09:Pub.2009.nat.dphy.optik.1optik.transv

Transverse angular momentum of photons - Aiello, Andrea; Marquardt, Christoph; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2010)
We develop the quantum theory of transverse angular momentum of light beams. The theory applies to paraxial and quasiparaxial photon beams in vacuum and reproduces the known results for classical beams when applied to coherent states of the field. Both the Poynting vector, alias the linear momentum, and the angular-momentum quantum operators of a light beam are calculated including contributions from first-order transverse derivatives. This permits a correct description of the energy flow in the beam and the natural emergence of both the spin and the angular momentum of the photons. We show that for collimated beams of light, orbital angular-momentum operators do not satisfy the standard commutation rules. Finally, we discuss the application of our theory to some concrete cases. © 2010 The American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Trojan-horse attacks threaten the security of practical quantum cryptography - Jain, Nitin; Anisimova, Elena; Khan, Imran; Makarov, Vadim; Marquardt, Christoph; Leuchs, Gerd (New Journal of Physics, 2014)
A quantum key distribution (QKD) system may be probed by an eavesdropper Eve by sending in bright light from the quantum channel and analyzing the back-reflections. We propose and experimentally demonstrate a setup for mounting such a Trojan-horse attack. We show it in operation against the quantum cryptosystem Clavis2 from ID Quantique, as a proof-of-principle. With just a few back-reflected photons, Eve discerns Bob's (secret) basis choice, and thus the raw key bit in the Scarani-Acín-Ribordy-Gisin 2004 protocol, with higher than 90% probability. This would clearly breach the security of the cryptosystem. Unfortunately, Eve's bright pulses have a side effect of causing a high level of afterpulsing in Bob's single-photon detectors, resulting in a large quantum bit error rate that effectively protects this system from our attack. However, in a Clavis2-like system equipped with detectors with less-noisy but realistic characteristics, an attack strategy with positive leakage of the key would exist. We confirm this by a numerical simulation. Both the eavesdropping setup and strategy can be generalized to attack most of the current QKD systems, especially if they lack proper safeguards. We also propose countermeasures to prevent such attacks.
CRIS-Team Scopus Importer:2022-06-05
Keywords: quantum cryptography; quantum hacking; quantum key distribution; reflectometry; security proofs; Trojan horse

Unfolding the Hong-Ou-Mandel interference between heralded photons from narrowband twin beams - Laiho, Kaisa; Dirmeier, Thomas; Shafiee, Golnoush; Marquardt, Christoph (New Journal of Physics, 2023)
The Hong-Ou-Mandel (HOM) interference is one of the most intriguing quantum optical phenomena and crucial in performing quantum optical communication and computation tasks. Lately, twin beam emitters such as those relying on the process of parametric down-conversion (PDC) have become confident sources of heralded single photons. However, if the pump power is high enough, the pairs produced via PDC—often called signal and idler—incorporate multiphoton contributions that usually distort the investigated quantum features. Here, we derive the temporal characteristics of the HOM interference between heralded states from two independent narrowband PDC sources. Apart from the PDC multiphoton content, our treatment also takes into account effects arriving from an unbalanced beam splitter ratio and optical losses. We perform a simulation in the telecommunication wavelength range and provide a useful tool for finding the optimal choice for PDC process parameters. Our results offer insight in the properties of narrowband PDC sources and turn useful when driving quantum optical applications with them.<br

Whispering gallery mode optical parametric oscillators - Marquardt, Christoph (Optics InfoBase Conference Papers, 2013)
Crystalline whispering gallery resonators with strong second order nonlinearities offer highly efficient and tuneable nonlinear processes in a very compact and stable setup. I will give an introduction and review recent developments. © OSA 2013.
CRIS-Team Scopus Importer:2022-06-05

Witnessing quantum squeezing with binary Homodyne detection - Müller, Christian R.; Seshadreesan, Kaushik P.; Peuntinger, Christian; Leuchs, Gerd; Marquardt, Christoph (Optics InfoBase Conference Papers, 2017)
CRIS-Team Scopus Importer:2022-06-05